Method for selecting a combination of backlight source and polarizing plate in image display device and liquid crystal display device

JP2022180382A5Active Publication Date: 2025-02-17TOYOBO CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022135289
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-01-12
Filing Date
2022-08-26
Publication Date
2025-02-17
Estimated Expiration
2042-03-17

AI Technical Summary

Technical Problem

Liquid crystal display devices using KSF phosphors with sharp emission peaks in the red region suffer from color spots and interference colors, particularly when viewed obliquely or when the power is off, due to the interaction between the high-retardation polyester film and the polarizer protective film.

Method used

The use of polarizing plates with specific retardation values and compatibility indices, such as FI(45), FI(30), and FI(60), along with controlled retardation ranges and surface properties to minimize color spots and interference colors, especially when using KSF phosphors as a backlight source.

Benefits of technology

The solution effectively suppresses color spots and interference colors, ensuring a wide reproduction color gamut, high transparency, and uniform color tone, even when viewed obliquely, particularly in large-sized display devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000068_0000
    Figure 00000068_0000
Patent Text Reader

Abstract

To provide a liquid crystal display device which has a wide reproducible color gamut and in which color spots are not noticeable even when an image display device emits a steep emission spectrum in the red region, and in which color spots are not noticeable even when a light source having a steep emission spectrum in the red region, such as a KSF phosphor, is used as a backlight light source. [Solution] An image display device having an image display cell and at least one polarizing plate, wherein the at least one polarizing plate is one in which light incident on the polarizing plate has a plurality of peak groups in the range of 600 to 650 nm, and the polarizing plate has a polarizer protective film whose 45-degree light source compatibility index (FI(45)) calculated by the following formula 1 is 0.4 or more and 0.62 or less. FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an image display device. More specifically, the present invention relates to an image display device that emits an emission spectrum having a steep peak in the red region, and more particularly to a liquid crystal display device that has a wide expressive range on the CIE (International Commission on Illumination) chromaticity diagram by using a light source having a steep peak in the red region in its emission spectrum. [Background technology]

[0002] It was known that when birefringent films such as polyester films were used under fluorescent or cold cathode tube light sources, iridescence caused by retardation would occur. For this reason, optically isotropic cellulose-based films have been used as protective films for polarizers used in liquid crystal displays and the like.

[0003] In recent years, a technology has been proposed to eliminate iridescence in liquid crystal displays by combining a polarizer plate using a polyester film with in-plane retardation of 3000 to 30000 nm as a polarizer protective film with a white light source having a continuous emission spectrum (for example, Patent Document 1). This technology has been highly evaluated for the excellent properties of polyester as a polarizer protective film, such as its superior mechanical strength, transparency, low moisture absorption, and low moisture permeability. Furthermore, with the decrease in cost and widespread use of white light-emitting diodes that combine blue light-emitting diodes and yellow phosphors, it has been put into practical use as a liquid crystal display. Recently, there has been a growing demand for wider color reproduction in liquid crystal displays, and light sources with a steep emission peak in the red region of their emission spectrum, known as KSF phosphors (phosphors with Mn added to K2SiF6 crystals), have been increasingly adopted as white light-emitting diodes. However, when a polarizer with a high retardation polyester film as a polarizer protective film is combined with a light source containing this KSF phosphor, red striped color patches are observed in some areas, indicating that further improvements are needed to suppress these color patches. In liquid crystal display devices using such KSF light sources, methods for suppressing color unevenness have been proposed, such as setting the refractive index of the polyester film in the transmission axis direction of the polarizer to 1.53 to 1.62 (for example, Patent Document 2), and providing an anti-reflective layer and / or a low-reflective layer on at least one surface of the polyester film (for example, Patent Document 3). However, there is still room for further improvement. In particular, when a polyester film is used for the polarizer on the light source side, color unevenness is likely to occur, and further improvement is required. Furthermore, with high-definition image display devices such as 4K and 8K, even large image display devices are often viewed up close, making even minor flaws noticeable, and improvements to these flaws are required. In order to take advantage of the characteristics of wide-color-gamut image display devices, high transparency is also required for the polarizer protective film. Furthermore, in black areas or when the power is off, interference colors caused by light interference in the coating layer of the polarizer protective film become noticeable, and these interference colors also lead to a decrease in display image quality and a decline in the overall appearance of the display device itself. Large image display devices, in particular, are often used in shop windows, the lobbies of luxury hotels, and high-end stores, and therefore require an excellent appearance even when the power is off. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] International Publication No. 2011 / 162198 [Patent Document 2] International Publication No. 2017 / 010444 [Patent Document 3] International Publication No. 2017 / 065148 [Overview of the Initiative] [Problems that the invention aims to solve]

[0005] One object of the present invention is to provide an image display device that exhibits no noticeable color unevenness and has a wide color gamut, even when using an image display device that emits an emission spectrum having a steep peak in the red region, and furthermore, an image display device in which interference colors are not noticeable when the light is turned off. A further object of the present invention is to provide a liquid crystal display device that exhibits no noticeable color unevenness and has a wide color gamut, even when using a light source having an emission spectrum in which a steep peak appears in the red region, such as a KSF phosphor, as the backlight light source, and furthermore, a liquid crystal display device in which interference colors are not noticeable when the light is turned off. The present invention may also aim to provide an image display device in which defects are not noticeable even in high-definition image display devices. Furthermore, the present invention may also aim to provide an image display device that can reproduce vivid colors with high transparency. In addition, the present invention may also aim to provide an image display device that exhibits uniform color tones, in which color unevenness is less likely to occur across the entire screen even when viewed from an oblique angle, especially in large display devices. [Means for solving the problem]

[0006] The inventors of this invention have diligently studied and developed the present invention to achieve the above objective. That is, the present invention encompasses the following aspects.

[0007] Section 1: An image display device having an image display cell and at least one polarizing plate, An image display device wherein at least one polarizer is a polarizer in which light incident on the polarizer has multiple peak groups in the range of 600 to 650 nm, and has a polarizer protective film whose 45-degree light source compatibility index (FI(45)) calculated by the following formula 1 is 0.4 or more and 0.62 or less. FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1 Rob(45): The retardation when the polarizer protective film is measured at a 45-degree angle from the slow phase axis direction toward the fast phase axis direction in the film plane direction, and tilted 50 degrees from the normal direction. Wd: Inter-peak distance (nm) of peak groups Wc: Mid-wavelength of the peak group (nm)

[0008] Item 2: The image display device according to Item 1, wherein both the 30-degree light source conformity index (FI(30)) obtained by the following formula 2 and the 60-degree light source conformity index (FI(60)) obtained by the following formula 3 of the polarizer protection film are 0.35 or more and 0.68 or less. FI(30)=Wd / 〔Wc / (Rob(30) / Wc)〕 Formula 2 FI(60)=Wd / 〔Wc / (Rob(60) / Wc)〕 Formula 3 Rob(30): Retardation when the polarizer protection film is measured from a direction inclined 50 degrees from the normal direction at an angle of 30 degrees from the slow axis direction to the fast axis direction in the film plane direction Rob(60): Retardation when the polarizer protection film is measured from a direction inclined 50 degrees from the normal direction at an angle of 60 degrees from the slow axis direction to the fast axis direction in the film plane direction Wd: Peak-to-peak distance of the peak group (nm) Wc: Central wavelength of the peak group (nm)

[0009] Item 3: The image display device according to Item 2, wherein the ratio (ΔFI / FI(45)) of the difference (ΔFI = FI(60) - FI(30)) between FI(30) and FI(60) with respect to FI(45) of the polarizer protection film is 0.2 or more and 0.35 or less.

[0010] Item 4: An image display device having an image display cell and at least one polarizing plate, wherein the at least one polarizing plate is a polarizing plate in which light incident on the polarizing plate has a plurality of peak groups in the range of 600 to 650 nm, the at least one polarizing plate has a polarizer and at least one polarizer protection film, and both values obtained by measuring the 45-degree light source conformity index (FI(45)) obtained by the following formula 1 of the at least one polarizer protection film at intervals of 100 mm along the long side direction and at intervals of 100 mm along the short side direction are 0.4 or more and 0.62 or less. An image display device in which the value obtained by subtracting the minimum value from the maximum value of the FI(45) measured at 100 mm intervals along the long side, and the value obtained by subtracting the minimum value from the maximum value of the FI(45) measured at 100 mm intervals along the short side, are both 0.026 or less. FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1 Rob(45): The retardation when the polarizer protective film is measured at a 45-degree angle from the slow phase axis direction toward the fast phase axis direction in the film plane direction, and tilted 50 degrees from the normal direction. Wd: Inter-peak distance (nm) of peak groups Wc: Mid-wavelength of the peak group (nm)

[0011] Section 5: The image display device according to item 4, wherein the 30-degree light source compatibility index (FI(30)) determined by the following formula 2 and the 60-degree light source compatibility index (FI(60)) determined by the following formula 3 of the polarizer protective film are both 0.35 or more and 0.68 or less, and the values ​​of these values ​​measured at 100 mm intervals along the long side and along the short side are both 0.35 or more and 0.68 or less. FI(30)=Wd / [Wc / (Rob(30) / Wc)] Equation 2 FI(60)=Wd / [Wc / (Rob(30) / Wc)] Equation 3 Rob(30): The retardation when the polarizer protective film is measured at an angle of 30 degrees in the film plane direction from the slow phase axis direction toward the fast phase axis direction, and tilted 50 degrees from the normal direction. Rob(60): The retardation when the polarizer protective film is measured from a direction tilted 50 degrees from the normal direction, at an angle of 60 degrees from the slow phase axis toward the fast phase axis in the film plane direction. Wd: Inter-peak distance (nm) of peak groups Wc: Mid-wavelength of the peak group (nm)

[0012] Item 6: The image display device according to item 5, wherein the ratio of ΔFI / FI(45), which is the difference between FI(30) and FI(60) (ΔFI=FI(60)-FI(30)) to FI(45) of at least one polarizer protective film, is measured at 100 mm intervals along the long side and at 100 mm intervals along the short side, and both values ​​are 0.2 or more and 0.35 or less.

[0013] Section 7: The image display device according to any one of items 1 to 6, wherein the polarizer protective film has one or fewer foreign objects with a major axis of 100 μm or more.

[0014] Section 8: The image display device according to any one of claims 1 to 7, wherein the amount of antimony atoms in the residue insoluble in the mixed solvent of parachlorophenol and tetrachloroethane in the polarizer protective film is 50 mg or less per 1 kg of resin constituting the polarizer protective film.

[0015] Section 9: The image display device according to any one of claims 1 to 8, wherein the polarizer protective film has an easily adhesive layer containing particles with a refractive index of 1.7 to 3 on at least one surface.

[0016] Section 10: The image display device according to any one of claims 1 to 9, wherein the light incident on the polarizing plate, having multiple peak groups in the range of 600 to 650 nm, originates from the excitation emission of a red phosphor activated with tetravalent manganese ions.

[0017] Section 11: An image display device having an image display cell and at least one polarizing plate, The at least one polarizer plate has a polarizer protective film in which the retardation (Rob(45)) measured from a direction tilted 50 degrees from the normal direction, at an angle of 45 degrees from the slow phase axis direction toward the fast phase axis direction in the film plane direction, is between 7500 nm and 11700 nm. An image display device comprising light incident on at least one polarizing plate, which includes excitation emission of a red phosphor activated with tetravalent manganese ions.

[0018] Section 12: An image display device having an image display cell and at least one polarizing plate, The aforementioned at least one polarizing plate has a polarizer and at least one polarizer protective film, The retardation (Rob(45)) of at least one polarizer protective film, measured at a 45-degree angle from the slow-phase axis direction toward the fast-phase axis direction in the film plane direction and tilted 50 degrees from the normal direction, is measured at 100 mm intervals along the long side and at 100 mm intervals along the short side, and both values ​​are between 7500 nm and 11700 nm. The value obtained by subtracting the minimum value from the maximum value of the values ​​measured along the long side of Rob(45) at 100 mm intervals, and the value obtained by subtracting the minimum value from the maximum value of the values ​​measured along the short side of Rob(45) at 100 mm intervals, are both 500 nm or less. An image display device comprising light incident on at least one polarizing plate, which includes excitation emission of a red phosphor activated with tetravalent manganese ions.

[0019] Section 13: The image display device according to item 11 or 12, wherein the polarizer protective film has one or fewer foreign objects with a major axis of 100 μm or more.

[0020] Section 14: The image display device according to any one of claims 11 to 13, wherein the amount of antimony atoms in the residue insoluble in the mixed solvent of parachlorophenol and tetrachloroethane in the polarizer protective film is 50 mg or less per 1 kg of resin constituting the polarizer protective film.

[0021] Section 15: The image display device according to any one of claims 11 to 14, wherein the polarizer protective film has an easily adhesive layer containing particles with a refractive index of 1.7 to 3 on at least one surface.

[0022] Section 16: The red phosphor activated with the aforementioned tetravalent manganese ions is K2SiF6:Mn 4+ An image display device according to any one of items 11 to 15, wherein the red phosphor is as shown.

[0023] Section 17: The image display device according to any one of claims 11 to 16, wherein the haze of the polarizer protective film is 5% or less.

[0024] Section 18: The image display device according to any one of claims 11 to 17, wherein the surface roughness (SRa) of at least one surface of the polarizer protective film is 0.05 μm or less.

[0025] Section 19: The image display device according to any one of claims 11 to 18, wherein the polarizing plate having the polarizer protective film has an angle (acute angle side) between the slow axis in the film surface of the polarizer protective film and the absorption axis of the polarizer, which is 83 degrees or more and 90 degrees or less, or 0 degrees or more and 7 degrees or less.

[0026] Section 20: The image display device according to any one of claims 11 to 19, wherein the polarizing plate is a polarizing plate having a λ / 4 wavelength layer on the side of the polarizer opposite to the side on which the polarizer protective film is laminated.

[0027] Section 21: An electroluminescent image display device, as described in any of items 1 to 20.

[0028] Section 22: A liquid crystal display device having a backlight source, a polarizing plate on the light source side, a liquid crystal cell, and a polarizing plate on the viewing side, The emission spectrum of the aforementioned backlight light source has multiple peak groups in the range of 600 to 650 nm. A liquid crystal display device in which at least one of the light source-side polarizer and the viewing-side polarizer is a polarizer having a polarizer protective film with a 45-degree light source compatibility index (FI(45)) of 0.4 or more and 0.62 or less, as determined by the following formula 1. FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1 Rob(45): The retardation when the polarizer protective film is measured at a 45-degree angle from the slow phase axis direction toward the fast phase axis direction in the film plane direction, and tilted 50 degrees from the normal direction. Wd: Inter-peak distance (nm) of peak groups Wc: Mid-wavelength of the peak group (nm)

[0029] Section 23: The liquid crystal display device according to item 22, wherein the polarizer protective film has a 30-degree light source compatibility index (FI(30)) determined by the following formula 2, and a 60-degree light source compatibility index (FI(60)) determined by the following formula 3, both of which are 0.35 or more and 0.68 or less. FI(30)=Wd / [Wc / (Rob(30) / Wc)] Equation 2 FI(60)=Wd / [Wc / (Rob(60) / Wc)] Equation 3 Rob(30): The retardation when the polarizer protective film is measured at an angle of 30 degrees in the film plane direction from the slow phase axis direction toward the fast phase axis direction, and tilted 50 degrees from the normal direction. Rob(60): The retardation when the polarizer protective film is measured from a direction tilted 50 degrees from the normal direction, at an angle of 60 degrees from the slow phase axis toward the fast phase axis in the film plane direction. Wd: Inter-peak distance (nm) of peak groups Wc: Mid-wavelength of the peak group (nm)

[0030] Section 24: The liquid crystal display device according to item 23, wherein the polarizer protective film has a ratio (ΔFI / FI(45)) of the difference between FI(30) and FI(60) with respect to FI(45) (ΔFI=FI(60)-FI(30)) of 0.2 or more and 0.35 or less.

[0031] Section 25: The liquid crystal display device according to any one of items 22 to 24, wherein the viewing-side polarizing plate is a polarizing plate having a polarizer protective film whose 45-degree light source compatibility index (FI(45)) determined by formula 1 is 0.4 or more and 0.62 or less.

[0032] Section 26: The liquid crystal display device according to any one of items 22 to 25, wherein the light source-side polarizing plate is a polarizing plate having a polarizer protective film whose 45-degree light source compatibility index (FI(45)) determined by formula 1 is 0.4 or more and 0.62 or less.

[0033] Section 27: A liquid crystal display device having a backlight source, a polarizing plate on the light source side, a liquid crystal cell, and a polarizing plate on the viewing side, The emission spectrum of the aforementioned backlight light source has multiple peak groups in the range of 600 to 650 nm. At least one of the light source-side polarizer and the viewing-side polarizer has a polarizer and at least one polarizer protective film. The 45-degree light source compatibility index (FI(45)) of at least one polarizer protective film, calculated using the following formula 1, is measured at 100 mm intervals along the long side and at 100 mm intervals along the short side, and both values ​​are between 0.4 and 0.62. A liquid crystal display device in which the value obtained by subtracting the minimum value from the maximum value of the FI(45) measured at 100 mm intervals along the long side, and the value obtained by subtracting the minimum value from the maximum value of the FI(45) measured at 100 mm intervals along the short side, are both 0.026 or less. FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1 Rob(45): The retardation when the polarizer protective film is measured at a 45-degree angle from the slow phase axis direction toward the fast phase axis direction in the film plane direction, and tilted 50 degrees from the normal direction. Wd: Inter-peak distance (nm) of peak groups Wc: Mid-wavelength of the peak group (nm)

[0034] Section 28: The liquid crystal display device according to item 27, wherein the 30-degree light source compatibility index (FI(30)) determined by the following formula 2 and the 60-degree light source compatibility index (FI(60)) determined by the following formula 3 of the polarizer protective film are both 0.35 or more and 0.68 or less, and the values ​​of these values ​​measured at 100 mm intervals along the long side and along the short side are both 0.35 or more and 0.68 or less. FI(30)=Wd / [Wc / (Rob(30) / Wc)] Equation 2 FI(60)=Wd / [Wc / (Rob(30) / Wc)] Equation 3 Rob(30): The retardation when the polarizer protective film is measured at an angle of 30 degrees in the film plane direction from the slow phase axis direction toward the fast phase axis direction, and tilted 50 degrees from the normal direction. Rob(60): The retardation when the polarizer protective film is measured from a direction tilted 50 degrees from the normal direction, at an angle of 60 degrees from the slow phase axis toward the fast phase axis in the film plane direction. Wd: Inter-peak distance (nm) of peak groups Wc: Mid-wavelength of the peak group (nm)

[0035] Section 29: The liquid crystal display device according to item 28, wherein the ratio ΔFI / FI(45), which is the ratio of the difference between FI(30) and FI(60) (ΔFI=FI(60)-FI(30)) to FI(45) of at least one polarizer protective film, is 0.2 or more and 0.35 or less when measured at 100 mm intervals along the long side and along the short side.

[0036] Section 30: The aforementioned polarizing plate on the viewing side, The 45-degree light source suitability index (FI(45)) obtained by formula 1 above is measured at 100 mm intervals along the long side and at 100 mm intervals along the short side, and both are between 0.4 and 0.62. The value obtained by subtracting the minimum value from the maximum value of the FI(45) measured at 100 mm intervals along the long side, and the value obtained by subtracting the minimum value from the maximum value of the FI(45) measured at 100 mm intervals along the short side, are both 0.026 or less. A liquid crystal display device according to any one of items 27 to 29, wherein the polarizer plate has a polarizer protective film.

[0037] Section 31: The light source side polarizing plate, The 45-degree light source suitability index (FI(45)) obtained by formula 1 above is measured at 100 mm intervals along the long side and at 100 mm intervals along the short side, and both are between 0.4 and 0.62. The value obtained by subtracting the minimum value from the maximum value of the FI(45) measured at 100 mm intervals along the long side, and the value obtained by subtracting the minimum value from the maximum value of the FI(45) measured at 100 mm intervals along the short side, are both 0.026 or less. A liquid crystal display device according to any one of items 27 to 30, which is a polarizing plate having a polarizer protective film.

[0038] Section 32: The liquid crystal display device according to any one of items 22 to 31, wherein the polarizer protective film has one or fewer foreign objects with a major axis of 100 μm or more.

[0039] Section 33: The liquid crystal display device according to any one of claims 22 to 32, wherein the amount of antimony atoms in the residue insoluble in the mixed solvent of parachlorophenol and tetrachloroethane in the polarizer protective film is 50 mg or less per 1 kg of resin constituting the polarizer protective film.

[0040] Section 34: The liquid crystal display device according to any one of claims 22 to 33, wherein the polarizer protective film has an easily adhesive layer containing particles with a refractive index of 1.7 to 3 on at least one surface.

[0041] Section 35: The liquid crystal display device according to any one of items 22 to 34, wherein the backlight source causes a red phosphor activated with tetravalent manganese ions to emit light when excited by light.

[0042] Section 36: The aforementioned backlight light source is activated by K2SiF6:Mn 4+ A liquid crystal display device according to item 35, which causes a red phosphor indicated by to emit light.

[0043] Section 37: A liquid crystal display device having a backlight source, a polarizing plate on the light source side, a liquid crystal cell, and a polarizing plate on the viewing side, The aforementioned backlight source emits light from a red phosphor activated with tetravalent manganese ions by excitation light. A liquid crystal display device in which at least one of the light source-side polarizer and the viewing-side polarizer is a polarizer protective film having a retardation (Rob(45)) of 7500 nm to 11700 nm when measured from a direction tilted 50 degrees from the normal direction at a 45-degree angle from the slow-phase axis direction to the fast-phase axis direction in the film plane direction.

[0044] Section 38: The liquid crystal display device according to item 37, wherein both Rob(30) and Rob(60) of the polarizer protective film are between 6570 nm and 12200 nm.

[0045] Section 39: The liquid crystal display device according to item 38, wherein the difference between Rob(30) and Rob(60) of the polarizer protective film (ΔRob = Rob(60) - Rob(30)) is 1880 nm or more and 3400 nm or less.

[0046] Section 40: The liquid crystal display device according to any one of claims 37 to 39, wherein the viewing-side polarizing plate is a polarizing plate having a polarizer protective film of Rob(45) between 7500 nm and 11700 nm.

[0047] Section 41: The liquid crystal display device according to any one of claims 37 to 40, wherein the light source-side polarizing plate is a polarizing plate having a polarizer protective film of Rob(45) between 7500 nm and 11700 nm.

[0048] Section 42: A liquid crystal display device having a backlight source, a polarizing plate on the light source side, a liquid crystal cell, and a polarizing plate on the viewing side, The aforementioned backlight source emits light from a red phosphor activated with tetravalent manganese ions by excitation light. At least one of the light source-side polarizer and the viewing-side polarizer has a polarizer and at least one polarizer protective film. The retardation (Rob(45)) of at least one polarizer protective film, measured at a 45-degree angle from the slow-phase axis direction toward the fast-phase axis direction in the film plane direction and tilted 50 degrees from the normal direction, is measured at 100 mm intervals along the long side and at 100 mm intervals along the short side, and both values ​​are between 7500 nm and 11700 nm. A liquid crystal display device in which the value obtained by subtracting the minimum value from the maximum value of the Rob(45) measured at 100 mm intervals along the long side, and the value obtained by subtracting the minimum value from the maximum value of the Rob(45) measured at 100 mm intervals along the short side, are both 500 nm or less.

[0049] Section 43: The liquid crystal display device according to item 42, wherein the values ​​of Rob(30) and Rob(60) of the polarizer protective film measured at 100 mm intervals along the long side direction and the values ​​measured at 100 mm intervals along the short side direction are all between 6570 nm and 12200 nm.

[0050] Section 44: The liquid crystal display device according to item 43, wherein the difference between Rob(30) and Rob(60) (ΔRob = Rob(60) - Rob(30)) of the polarizer protective film is measured at 100 mm intervals along the long side and at 100 mm intervals along the short side, and both of these values ​​are between 1880 nm and 3400 nm.

[0051] Section 45: The liquid crystal display device according to any one of claims 37 to 44, wherein the viewing-side polarizing plate is a polarizing plate having a polarizer protective film in which both the values ​​measured along the long side direction of Rob(45) at 100 mm intervals and the values ​​measured along the short side direction at 100 mm intervals are between 7500 nm and 11700 nm.

[0052] Section 46: The liquid crystal display device according to any one of claims 37 to 45, wherein the light source-side polarizing plate is a polarizing plate having a polarizer protective film in which both the values ​​measured along the long side direction of Rob(45) at 100 mm intervals and the values ​​measured along the short side direction of Rob(45) are between 7500 nm and 11700 nm.

[0053] Section 47: The liquid crystal display device according to any one of claims 37 to 46, wherein the polarizer protective film has one or fewer foreign objects with a major axis of 100 μm or more.

[0054] Section 48: The liquid crystal display device according to any one of claims 37 to 47, wherein the amount of antimony atoms in the residue insoluble in the mixed solvent of parachlorophenol and tetrachloroethane in the polarizer protective film is 50 mg or less per 1 kg of resin constituting the polarizer protective film.

[0055] Section 49: The liquid crystal display device according to any one of claims 37 to 48, wherein the polarizer protective film has an easily adhesive layer containing particles with a refractive index of 1.7 to 3 on at least one surface.

[0056] Section 50: The red phosphor activated with the aforementioned tetravalent manganese ions is K2SiF6:Mn 4+ A liquid crystal display device according to any one of items 37 to 49, wherein the red phosphor is represented by [the specified symbol].

[0057] Section 51: The image display device according to any one of claims 37 to 50, wherein the haze of the polarizer protective film is 5% or less.

[0058] Section 52: The image display device according to any one of claims 37 to 51, wherein the surface roughness (SRa) of at least one surface of the polarizer protective film is 0.05 μm or less.

[0059] Section 53: The liquid crystal display device according to any one of claims 37 to 52, wherein the haze of the polarizing plate having the polarizer protective film is 5% or less.

[0060] Section 54: A liquid crystal display device according to any one of claims 37 to 53, wherein the SRa on the surface of the polarizing plate having the polarizer protective film that is opposite to the liquid crystal cell is 0.05 μm or less.

[0061] Section 55: The liquid crystal display device according to any one of claims 37 to 54, wherein the SRz of the polarizer protective film is 1.0 μm or less.

[0062] Section 56: A liquid crystal display device according to any one of claims 37 to 55, wherein the SRz of the surface of the polarizing plate having the polarizer protective film that is opposite to the liquid crystal cell is 1.0 μm or less.

[0063] Section 57: A liquid crystal display device according to any one of claims 37 to 56, wherein the polarizer protective film has a functional layer on the side opposite to the polarizer, and the reflectance measured from the functional layer side is 5% or less.

[0064] Section 58: The liquid crystal display device according to any one of claims 37 to 57, wherein the light source-side polarizing plate or the viewing-side polarizing plate has an angle (acute angle side) between the slow axis in the film surface of the polarizer protective film and the absorption axis of the polarizer that is 83 degrees or more and 90 degrees or less, or 0 degrees or more and 7 degrees or less.

[0065] Section 59: A liquid crystal display device according to any one of claims 37 to 58, wherein either or both of the light source-side polarizing plate and the viewing-side polarizing plate have the resin film laminated on the side opposite to the liquid crystal cell of the polarizer, and a cured resin layer, an optical compensation layer, an adhesive layer, or a zero retardation resin film is laminated on the liquid crystal cell side of the polarizer.

[0066] Section 60: A liquid crystal display device having a backlight light source, a light source-side polarizing plate, a liquid crystal cell, and a viewing-side polarizing plate, a method for selecting a combination of a backlight light source and a polarizing plate, (a) A step of selecting a backlight light source having multiple peak groups in the range of 600 to 650 nm in its emission spectrum, and (b) A step of selecting a polarizer having a polarizer protective film, which is at least one of the light source side polarizer and the viewing side polarizer, and which has a 45-degree light source compatibility index (FI(45)) of 0.4 or more and 0.62 or less, as determined by the following formula 1. Methods that include... FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1 Rob(45): The retardation when the polarizer protective film is measured at a 45-degree angle from the slow phase axis direction toward the fast phase axis direction in the film plane direction, and tilted 50 degrees from the normal direction. Wd: Inter-peak distance (nm) of peak groups Wc: Mid-wavelength of the peak group (nm)

[0067] Section 61: A liquid crystal display device having a backlight light source, a light source-side polarizing plate, a liquid crystal cell, and a viewing-side polarizing plate, a method for selecting a combination of a backlight light source and a polarizing plate, (a) A step of selecting a backlight light source having multiple peak groups in the range of 600 to 650 nm in its emission spectrum, and (b) At least one of the light source side polarizer and the viewing side polarizer, A step of selecting a polarizer plate having a polarizer protective film, wherein the 45-degree light source compatibility index (FI(45)) calculated by the following formula 1 is such that the values ​​measured at 100 mm intervals along the long side and the values ​​measured at 100 mm intervals along the short side are both between 0.4 and 0.62, and the value obtained by subtracting the minimum value from the maximum value of the FI(45) measured at 100 mm intervals along the long side and the value obtained by subtracting the minimum value from the maximum value of the FI(45) measured at 100 mm intervals along the short side are both 0.026 or less. Methods that include... FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1 Rob(45): The retardation when the polarizer protective film is measured at a 45-degree angle from the slow phase axis direction toward the fast phase axis direction in the film plane direction, and tilted 50 degrees from the normal direction. Wd: Inter-peak distance (nm) of peak groups Wc: Mid-wavelength of the peak group (nm)

[0068] Section 62: The method according to item 60 or 61, wherein the polarizer protective film has one or fewer foreign particles with a major axis of 100 μm or more.

[0069] Section 63: The method according to any one of claims 60 to 62, wherein the amount of antimony atoms in the residue insoluble in the mixed solvent of parachlorophenol and tetrachloroethane in the polarizer protective film is 50 mg or less per 1 kg of resin constituting the polarizer protective film.

[0070] Section 64: The polarizer protective film has an easily adhering layer containing particles with a refractive index of 1.7 to 3 on at least one surface, according to any one of claims 60 to 63. [Effects of the Invention]

[0071] The present invention provides an image display device that emits an emission spectrum having a steep peak in the red region, yet exhibits minimal color unevenness, a wide color gamut, and minimal interference color when the device is turned off. In particular, even when using a backlight source such as a KSF phosphor, which has an emission spectrum exhibiting a steep peak in the red region, the present invention provides a liquid crystal display device that exhibits minimal color unevenness, particularly across the entire screen, a wide color gamut, and minimal interference color when the device is turned off. The present invention can provide an image display device in which defects are not noticeable even in high-definition image display devices. Furthermore, the present invention can provide an image display device with a wide color gamut that maximizes the use of highly transparent and vivid color reproduction. Moreover, the present invention can provide an image display device that exhibits uniform color tones, even when viewed from an oblique angle, particularly in large display devices, where color unevenness is less likely to occur across the entire screen. [Brief explanation of the drawing]

[0072] [Figure 1] This is the emission spectrum of a white LED having K2SiF6:Mn4+ as the red phosphor used in the example. [Modes for carrying out the invention]

[0073] (Image display device) In one embodiment, the image display device of the present invention is preferably an image display device in which the light incident on the polarizing plate has multiple peaks (particularly steep peaks) in the range of 600 to 650 nm. Examples of image display devices of the present invention include, but are not limited to, liquid crystal display devices, electroluminescent (EL) display devices, and micro-LEDs. In the image display device of the present invention, methods for emitting light having multiple peaks (particularly steep peaks) in the range of 600 to 650 nm include methods of exciting a phosphor capable of emitting light with multiple peaks (particularly steep peaks), such as a KSF phosphor (a phosphor obtained by adding Mn to a K2SiF6 crystal), and methods of using a semiconductor laser in combination.

[0074] In the case of liquid crystal display devices, for example, one method is to use a blue or ultraviolet LED to excite a red KSF phosphor and cause it to emit light, thereby creating a white light backlight source. In the case of electroluminescent display devices, examples include using a blue EL emitter to excite a red KSF phosphor and use it as a red pixel, or using a blue EL emitter to excite a red KSF phosphor and a green phosphor to produce white light, which is then converted into pixels of each color using color filters.

[0075] The present invention is not limited to its light emission method or drawing method, but as a representative image display device, a liquid crystal display device having a backlight light source, wherein the emission spectrum of the backlight light source has multiple steep peaks in the red region, will be given as an example and described in detail below. Note that the following description is not limited to liquid crystal displays unless otherwise specified.

[0076] (Backlight source) In the liquid crystal display device of the present invention, a backlight source having multiple steep peaks in the emission spectrum in the range of 600 to 650 nm is preferably used. Here, a steep peak means that the full width at half maximum (FWHM) is 6 nm or less, preferably 5 nm or less, and more preferably 4 nm or less. Note that the FWHM is the FWHM for one peak top. If two or more peaks are close together and the measured emission intensity overlaps in a portion of the peak top that is 1 / 2 or more, or if it overlaps with a broad peak, the FWHM is determined by extrapolating from the slope just before the overlap. The above-mentioned plurality of peaks (especially steep peaks) may form a peak group including adjacent peaks with an interval between peak tops of 7 nm or less (one peak may be an accompanying peak of the other peak). The peak group may be composed of only one single peak (also referred to as an independent peak), or may include a certain peak a (for example, an independent peak) and all peaks b (for example, accompanying peaks) existing within 7 nm from peak a at the interval between peak tops. The above-mentioned plurality of peaks (especially steep peaks) are preferably composed of a plurality of peak groups (for example, a combination of one or more peak groups composed of independent peaks and accompanying peaks and one or more peak groups composed of only independent peaks). Note that the determination methods for peak groups, independent peaks, and accompanying peaks are as described below.

[0077] As a specific backlight light source, for example, a light source of a method for emitting a red phosphor activated by tetravalent manganese ions with excitation light can be mentioned. The red phosphor activated by tetravalent manganese ions can emit red fluorescence when irradiated with excitation light. Examples of the light source used for excitation light include blue LEDs, ultraviolet LEDs, blue lasers, ultraviolet lasers, etc., and blue LEDs are preferred. As the blue LED, a nitride-based semiconductor blue LED used in a method for emitting a general yellow phosphor can be preferably used.

[0078] As the red phosphor activated by tetravalent manganese ions, a metal fluoride compound activated by tetravalent manganese ions is more preferred, such as Mn 4+ activated Mg fluorogermanate phosphor (2.5MgO·MgF2:Mn 4+ )、M 1 2M 2 F6:Mn 4+ (each M 1 is independently selected from Li, Na, K, Rb, and Cs; M 2 is selected from Si, Ge, Sn, Ti, Zr, Nb, and Ta) phosphors are mentioned as suitable phosphors. Specific examples of these include KNaMF6:Mn 4+ (M: Nb or Ta), KRbSiF6:Mn4+ , K2SiF6:Mn 4+ , K2TiF6:Mn 4+ Examples include K2SiF6:Mn, which is generally called KSF 4+ such as M 1 2M 2 F6:Mn 4+ phosphors are preferred.

[0079] In addition to the red phosphor activated by tetravalent manganese ions, the backlight source preferably contains a green phosphor. Examples of the green phosphor include Eu-activated chlorosilicate phosphor, Eu-activated silicate phosphor, Eu-activated β-sialon phosphor, Eu-activated thiogalate phosphor, rare earth aluminate phosphor, and lanthanum silicon nitride-based phosphor. The green phosphor may be green quantum dot particles. Among them, from the perspective of color reproduction range, Si 6-z Al z O z N 8-z : Eu (0 < z < 4.2) and other Eu-activated β-sialon phosphors or green quantum dot particles are preferred.

[0080] In addition to the red phosphor activated by tetravalent manganese ions, the backlight source may contain a yellow phosphor. Examples of the yellow phosphor include, for example, (Y or Lu)3(Al or Ga)5O 12 : Ce, (Y or Ce)3Al5O 12 and other YAG-based phosphors. Although white light can be emitted only by the combination of a blue LED and a yellow phosphor, the color gamut can be further expanded by combining this with a red phosphor activated by tetravalent manganese ions. These backlight sources may further include the above green phosphor to adjust the color balance.

[0081] The backlight light source of the present invention is preferably a light source (white LED) that excites and emits light from a red phosphor activated with tetravalent manganese ions using a blue LED as described above. However, it may also be a combination of a light source having a method of exciting and emitting light from a red phosphor activated with tetravalent manganese ions and a light source having another method, such as a combination of the white LED and a sheet containing at least one type of quantum dot of green and red, a combination of a blue LED and a sheet containing a green quantum dot and a red phosphor activated with tetravalent manganese ions, a combination of a magenta LED that excites and emits light from a red phosphor activated with tetravalent manganese ions using a blue LED and a sheet containing a green quantum dot, or a combination of the white LED and a white LED that emits light from a yellow phosphor or a white LED using an RGB three-wavelength method. In addition, the green phosphors listed above may be used instead of the green quantum dots in the above. In the following, the light source described above will sometimes be referred to as the KSF light source.

[0082] As a liquid crystal display device, for example, it may be a direct-lit system in which the above-mentioned light source is placed directly below the liquid crystal panel, or it may be an edge-lit system in which the above-mentioned light source is placed on the side and illuminates through a light guide plate installed at the bottom of the liquid crystal panel.

[0083] Furthermore, it is preferable that the backlight source be incorporated into the liquid crystal display device as a light source unit by combining a reflector, diffuser, prism, lens plate, etc. In addition, a reflective polarizing plate may be provided between the backlight source and the liquid crystal panel to increase brightness.

[0084] (Polarizing plate) The liquid crystal display device of the present invention is preferably a liquid crystal display device having at least one polarizing plate on the backlight light source side (hereinafter, the backlight light source may simply be referred to as the light source) and on the viewing side of the liquid crystal cell. That is, the liquid crystal display device of the present invention preferably has a backlight light source, a light source side polarizing plate, a liquid crystal cell, and a viewing side polarizing plate. At least one of the light source side polarizing plate and the viewing side polarizing plate preferably has a polarizer and at least one polarizer protective film, and usually the polarizer protective film is laminated on at least one side of the polarizer. (Polarizer protective film) The 45-degree light source compatibility index (FI(45)) of the polarizer protective film, as calculated by the following formula 1, is preferably 0.4 or more and 0.62 or less. FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1 In Equation 1, Rob(45), Wd, and Wc are as follows: Rob(45): The retardation when the polarizer protective film is measured at a 45-degree angle from the slow phase axis direction toward the fast phase axis direction in the film plane direction, and tilted 50 degrees from the normal direction. Wd: Inter-peak distance (nm) of peak groups located in the 600-650nm range of the backlight source. Wc: The median wavelength (nm) of the peak group located in the 600-650nm range of the backlight source.

[0085] It is preferable that the 45-degree light source compatibility index (FI(45)) of the polarizer protective film, calculated using Equation 1, is between 0.4 and 0.62, both when measured at 100 mm intervals along the long side and along the short side. Note that the values ​​measured at 100 mm intervals along the long side and along the short side may be simply abbreviated as the values ​​for the long side and short side, respectively.

[0086] The FI(45) of the polarizer protective film is further preferred in the order of 0.43 or higher, 0.44 or higher, 0.445 or higher, 0.45 or higher, 0.455 or higher, and 0.46 or higher. The FI(45) of the polarizer protective film is further preferred in the order of 0.6 or less, 0.58 or less, 0.57 or less, 0.56 or less, 0.55 or less, and 0.54 or less. The values ​​of FI(45) of the polarizer protective film in the long and short side directions are preferably in the following order: 0.43 or higher, 0.44 or higher, 0.445 or higher, 0.45 or higher, and 0.455 or higher to 0.46 or higher. The values ​​of FI(45) of the polarizer protective film in the long and short side directions are further preferably 0.60 or less, 0.58 or less, 0.57 or less, 0.56 or less, 0.55 or less, and 0.54 or less, in that order. Furthermore, as explained below, "in order of preference" means that the narrower the range of values, the more preferable it is. By setting FI(45) within the above range, even when a high-retardation resin film is used as a polarizer protective film in a liquid crystal display device that uses a light source with a steep emission spectrum such as a KSF light source as a backlight, it is possible to effectively suppress color unevenness, which was previously considered difficult to achieve, resulting in a natural image even when viewed from an oblique direction, and furthermore, an image with uniform color tone even to the corners of the screen. Furthermore, it is preferable that both the value obtained by subtracting the minimum value from the maximum value of FI(45) measured at 100 mm intervals along the long side and the value obtained by subtracting the minimum value from the maximum value of FI(45) measured at 100 mm intervals along the short side are 0.026 or less, more preferably 0.024 or less, even more preferably 0.021 or less, particularly preferably 0.019 or less, and most preferably 0.016 or less. In addition, the values ​​obtained by subtracting the minimum value from the maximum value of the values ​​measured at 100 mm intervals along the long side, and the values ​​obtained by subtracting the minimum value from the maximum value of the values ​​measured at 100 mm intervals along the short side, are sometimes simply referred to as the variation in the long side direction and the variation in the short side direction, respectively. Furthermore, polarizer protective films having such FI(45) (in other words, high diagonal retardation) may be referred to as high-Re polarizer protective films or simply high-Re films.

[0087] Wd is preferably 8 nm or greater, more preferably 10 nm or greater, and even more preferably 12 nm or greater. Furthermore, Wd is preferably 40 nm or less, more preferably 35 nm or less, and even more preferably 30 nm or less.

[0088] Wc is preferably 605 nm or greater, more preferably 610 nm or greater, and even more preferably 615 nm or greater. Furthermore, Wc is preferably 645 nm or less, more preferably 640 nm or less, and even more preferably 635 nm or less.

[0089] Determination of Wd and Wc In the present invention, Wd and Wc are preferably determined by the following method. The emission spectrum of the backlight source shall be measured using a spectrophotometer with a measurement wavelength pitch within the range of 0.5 to 1 nm. In addition, the light intensity shall be adjusted using a light-reducing filter or the like to match the sensitivity characteristics of the photodetector so that the intensity does not saturate. 1. Selection of the main peak Among the peaks in the range of 600nm to 650nm, read the peak wavelength and intensity of the peak with the highest intensity (Pmax). If the intensity difference between adjacent wavelengths is approximately the same, the midpoint of the two points is taken as the peak wavelength, and the higher value is used as the peak wavelength intensity. Here, "approximately the same intensity difference" means that the intensity difference is 10% or less of the highest intensity peak.

[0090] 2. Selection of secondary peaks Select a peak with an intensity of 1 / 10 or more of the Pmax intensity within the range of 600nm to 650nm, and read its wavelength and intensity. In this case as well, if the intensity difference between adjacent wavelengths measured is approximately the same, proceed as in step 1.

[0091] 3. Intensity correction The intensity value of the peak selected in step 2 is multiplied by the spectral sensitivity efficiency value shown in "Table 1 - Determination value of spectral luminous efficiency V(λ) in photopic view" of JIS Z 8785:2019 [ISO 23539:2005 (CIE S 010:2004)], and this value is used as the corrected intensity. Note that since Table 1 of JIS is in 1 nm increments, the spectral sensitivity efficiency is used for the wavelength obtained by rounding the peak wavelength to the first decimal place.

[0092] 4. Creating peak groups From the sub-peaks selected in step 2, choose one peak. This peak will be called Peak A. If there is a peak (let's call this Peak B) within 7 nm of Peak A with a correction intensity greater than Peak A's own correction intensity, Peak A will be considered an associated peak of Peak B. If there are multiple peaks within 7 nm of Peak A with a correction intensity greater than Peak A's own correction intensity, the peak closest to Peak A will be called Peak B, and Peak A will be considered an associated peak of Peak B (if the proximity is the same, the one with the greater correction intensity will be called Peak B, and Peak A will be an associated peak of Peak B). If the associated peak (Peak B in the above sense) is an associated peak of another peak (let's call this Peak C), then they together (i.e., both Peak A and Peak B) will be considered associated peaks of Peak C. If there are no peaks within 7 nm of Peak A with a correction intensity greater than Peak A's own correction intensity, Peak A will be considered an independent peak. The primary peak is also an independent peak. All sub-peaks are classified as either independent peaks or associated peaks, and independent peaks and their associated peaks form a peak group. If no associated peaks exist, an independent peak alone will also form a peak group.

[0093] 5. Determination of peak group intensity The correction intensities of each peak (independent peak or associated peak) in the peak group determined by step 4 are summed up, and this value is defined as the peak group intensity.

[0094] 6. Determination of the peak wavelengths of the peak group The sum of the values ​​obtained by multiplying the peak wavelength of each peak (independent or associated peak) in a peak group by its correction intensity is divided by the sum of the individual peak intensities. The resulting value is defined as the peak wavelength of that peak group. The peak wavelength can be set to a value rounded to the third decimal place.

[0095] 7. Determination of the peak-to-group distance (Wd) Two peak groups are selected from those with the highest peak group intensities. The peak group with the greater intensity is designated as the first peak group, and the peak group with the smaller intensity is designated as the second peak group. The difference between the peak wavelengths of the first and second peak groups is calculated to one decimal place and used as the distance between the peak groups.

[0096] 8. Determination of the median wavelength (Wc) The average of the peak wavelengths of the first and second peak groups, rounded to one decimal place, is used as the median wavelength.

[0097] For example, let's explain this specifically using the KSF light source shown in Figure 1. The peak with the highest intensity (Pmax) was measured at a wavelength of 630.5 nm with an intensity of 1.000. At the adjacent wavelength of 631.2 nm, the intensity was measured at 0.916. Therefore, the peak wavelength of the main peak is (630.5 + 631.2) / 2 = 630.85. Rounding to two decimal places, this is 630.9 nm, and the intensity is 1.000. Sub-peaks with an intensity of 1 / 10 or more of the intensity of Pmax are: Sub-peak 1: Peak wavelength 608.6 nm (intensity 0.158), which is the midpoint between peak wavelength 608.2 nm (intensity 0.153) and peak wavelength 608.9 nm (intensity 0.158). Sub-peak 2: Peak wavelength 613.4 nm (intensity 0.368), Sub-peak 3: Peak wavelength 634.9 nm (intensity 0.698), Sub-peak 4: Peak wavelength 647.5 nm (intensity 0.195) That is the case.

[0098] Multiplying each value by the spectral sensitivity efficiency specified in JIS to obtain the correction intensity yields the following results. Sub-peak 1: Peak wavelength 608.6 nm (correction intensity: 0.158 × 0.515 = 0.081), Sub-peak 2: Peak wavelength 613.4 nm (Correction intensity: 0.368 × 0.465 = 0.171) Main peak: Peak wavelength 630.9 nm (Correction intensity: 1.000 × 0.244 = 0.244) Sub-peak 3: Peak wavelength 634.9 nm (Correction intensity: 0.698 × 0.217 = 0.151) Sub-peak 4: Peak wavelength 647.5 nm (Correction intensity: 0.195 × 0.118 = 0.023)

[0099] Sub-peak 3, with a peak wavelength of 634.9 nm, can be considered an associated peak of the main peak with a peak wavelength of 630.9 nm. These two peaks form the first peak group, with a peak group intensity of 0.395. Sub-peak 1, with a peak wavelength of 608.6 nm, can be considered an associated peak of sub-peak 2, with a peak wavelength of 613.4 nm. These two peaks form the second peak group, with a peak group intensity of 0.252. Sub-peak 4, with a peak wavelength of 647.5 nm, is an independent peak (a peak group on its own) with a peak group intensity of 0.023.

[0100] The peak wavelengths of the first peak group are: (630.9×0.244+624.9×0.151) / (0.244+0.151)=611.86nm This is the result. The peak wavelengths of the second peak group are: (608.6×0.081+613.4×0.171) / (0.081+0.171)=632.43nm This is the result. The peak-to-peak distance (Wd) is 20.6 nm, and the median wavelength (Wc) is 622.1 nm.

[0101] From these results, in the case of a light source using a metal fluorine compound activated with manganese ions, such as KSF, as a red phosphor, the Rob(45) of the polarizer protective film is preferably 7500 nm or higher, and more preferably 8100 nm or higher, 8280 nm or higher, 8380 nm or higher, 8470 nm or higher, and 8650 nm or higher in that order. Furthermore, the Rob(45) is preferably 11700 nm or lower, and more preferably 11300 nm or lower, 10900 nm or lower, 10720 nm or lower, 10530 nm or lower, 10340 nm or lower, and 10160 nm or lower in that order.

[0102] In the case of a light source using a metal fluorine compound activated with manganese ions, such as KSF, as a red phosphor, the values ​​of Rob(45) of the polarizer protective film in the long and short sides are preferably 7500 nm or more, and more preferably 8100 nm or more, 8280 nm or more, 8380 nm or more, 8470 nm or more, and 8650 nm or more, in that order. Furthermore, the values ​​of Rob(45) of the polarizer protective film in the long and short sides are preferably 11700 nm or less, and more preferably 11300 nm or less, 10900 nm or less, 10720 nm or less, 10530 nm or less, 10340 nm or less, and 10160 nm or less, in that order. Furthermore, the variation of Rob(45) of the polarizer protective film in the long-side and short-side directions is preferably 500 nm or less, more preferably 450 nm or less, even more preferably 400 nm or less, particularly preferably 350 nm or less, and most preferably 300 nm or less.

[0103] Although the above describes the case of a backlight light source for a liquid crystal display device, the 45-degree light source suitability index (FI(45)) can be similarly determined for light incident on a polarizing plate in an image display device. The spectrum of light can be measured, for example, by removing the backlight unit and emitting white light in the case of the backlight light source of a liquid crystal display device, or by removing the polarizing plate on the viewing side of the organic EL image display device from the organic EL image display device and emitting white light from the image display device. If the components between the backlight light source and the outermost surface of the image display device, or between the image display cell such as an organic EL cell and the outermost surface of the image display device, have uniform transmission characteristics in the 600-650 nm range, the spectrum of light emitted from the image display device can be used as a substitute. The same applies to the 30-degree light source compatibility index (FI(30)) and the 60-degree light source compatibility index (FI(60)) described below.

[0104] According to the inventors' research, the reason why color unevenness from oblique directions can be suppressed within such a specific retardation range is thought to be as follows, but the present invention is not limited to this reason. First, the reasons for the occurrence of color variations are thought to be as follows: When a high-Re polarizer protective film is used, the polarization selectivity of the reflectivity occurs not only in the polarizer and reflective polarizer plate, but also in the interfacial reflection between the high-Re polarizer protective film and air or other layers, resulting in a weak polarizing effect. In other words, the high-Re polarizer protective film is sandwiched between polarizers. When a polarizer is viewed from the front, the interface has almost no polarizing effect. However, as the viewing angle from the normal direction of the polarizer increases, the polarizing effect increases, reaching its maximum near the Brewster angle.

[0105] In polarizing plates, the absorption axis of the polarizer and the in-plane phase-advancing axis of the high-Re film are often bonded together. In this case, even if the viewing angle is tilted from the front along the slow phase-advancing axis of the high-Re film, the retardation of the high-Re film decreases, but the direction of polarization vibration is perpendicular to the phase-advancing axis of the high-Re film. Therefore, linear polarization is not disturbed by the high-Re film, and no color fringing occurs. Similarly, even if the viewing angle is tilted along the phase-advancing axis of the resin film, the retardation of the high-Re film increases, but the direction of polarization vibration is parallel to the slow phase-advancing axis of the resin film. Therefore, linear polarization is not disturbed by the high-Re film, and no color fringing occurs.

[0106] However, if we change the viewing angle from directly in front to an oblique angle in the direction of the leading axis within the film plane relative to the slow axis of the high-Re film, the shape of the refractive index ellipsoid of the high-Re film as viewed from an oblique direction changes as the viewing angle changes, causing the slow axis and leading axis to shift from the direction of polarization vibration. As a result, linearly polarized light that enters the high-Re film obliquely becomes elliptically polarized light, and the transmittance changes depending on the state of elliptically polarized light due to the action of the polarizer (or the action of the interface as a polarizer) when it exits the high-Re film. Hereafter, the angle in the film plane relative to the slow axis and the direction of the fast axis will be called the azimuth angle, and the angle relative to the normal direction of the film will be called the polar angle. Also, when simply referring to a diagonal direction, it may mean a direction that has a polar angle, regardless of the azimuth angle.

[0107] As shown in Equation 4 below, the transmittance depends on the wavelength and retardation. When the light source has a continuous and smooth emission spectrum, such as an LED using yellow phosphor, the envelope of the spectrum obtained by multiplying the transmittance at each wavelength by the original emission spectrum (the envelope of the intensity of light transmitted by the polarizer (or its polarizing action) after passing through the resin film) is similar to the spectral shape of the original light source. However, when the emission spectrum has steep peaks, such as a KSF light source, it becomes difficult for this envelope to reproduce the spectral shape of the original light source. When viewing an image, the azimuth angle and polar angle differ between the foreground and background, and left and right. The retardation changes with the angle, which changes the polarization state of the light that has passed through the high-Re film. This creates angles that transmit and block steep peaks, resulting in color variations.

[0108] T=cos 2 α-sin2βsin2(β-α)sin 2 (πRe / λ) (Equation 4) α: Angle formed by the absorption axes of the two polarizing plates. β: Angle between the absorption axis of the polarizer and the slow axis of the birefringent. λ: Wavelength T: Transmittance

[0109] According to Equation 4, in the retardation range of several thousand nanometers to tens of thousands of nanometers, the transmittance T will repeat between 0% and 100% with a period of several nanometers to tens of nanometers. In the KSF light source, as shown in Figure 1, there is a main peak group around 630 nm and a sub-peak group around 610 nm. If the period of transmittance T is such that the transmittance of one of these main peak group and sub-peak group is high and the transmittance of the other is low, then either the main peak group or the sub-peak group is always transmitted, and the amount of change in red light to the human eye is small, making it difficult to perceive as a color patch.

[0110] As mentioned above, color unevenness becomes noticeable when the azimuth angle is around 30-60 degrees and the angle from the normal direction exceeds 45 degrees. However, if the diagonal retardation of the high-Re polarizer protective film in this region is within the appropriate range, color unevenness can be suppressed.

[0111] As mentioned earlier, generally, when a birefringent film is tilted from the front direction (normal direction) in the direction of the slow phase axis, the diagonal retardation of the film becomes smaller than the in-plane retardation, and when tilted in the direction of the fast phase axis, it becomes larger. When tilted with an azimuthal angle in the direction of the fast phase axis, the retardation will be somewhere in between, depending on the degree of the azimuthal angle. It is believed that color variations can be effectively suppressed by adjusting the diagonal retardation in the areas where these color variations are likely to occur to a desirable range.

[0112] The polarizer protective film used in the present invention has a 30-degree light source compatibility index (FI(30)) determined by the following formula 2 and / or a 60-degree light source compatibility index (FI(60)) determined by the following formula 3, which is preferably 0.35 or higher and preferably 0.68 or lower. FI(30)=Wd / [Wc / (Rob(30) / Wc)] Equation 2 FI(60)=Wd / [Wc / (Rob(60) / Wc)] Equation 3 In equations 2 and 3, Rob(30) and Rob(60) are as follows, and Wd and Wc are as described above. Rob(30): Retardation when measuring the polarizer protective film from a direction tilted 50 degrees from the normal direction, at an angle of 30 degrees from the slow phase axis toward the fast phase axis in the film plane direction. Rob(60): Retardation when measuring a polarizer protective film at a 60-degree angle from the slow phase axis to the fast phase axis in the film plane, and tilted 50 degrees from the normal direction.

[0113] In the polarizer protective film used in the present invention, the values ​​of the 30-degree light source compatibility index (FI(30)) in the long and short sides, and / or the values ​​of the 60-degree light source compatibility index (FI(60)) in the long and short sides, are preferably 0.35 or higher and preferably 0.68 or lower.

[0114] The FI(30) and / or FI(60) of the polarizer protective film are more preferably 0.37 or higher, 0.38 or higher, 0.39 or higher, and 0.4 or higher, in that order. Furthermore, it is preferable that FI(30) and / or FI(60) are less than FI(45). The FI(30) and / or FI(60) of the polarizer protective film are more preferably 0.65 or less, 0.63 or less, 0.62 or less, 0.61 or less, and 0.6 or less, in that order. It is preferable that FI(30) and / or FI(60) exceed FI(45). The values ​​of FI(30) and / or FI(60) in the long and short sides of the polarizer protective film are preferably 0.37 or greater, 0.38 or greater, 0.39 or greater, and 0.4 or greater, in that order, and preferably less than the values ​​of FI(45) in the long and short sides. The values ​​of FI(30) and / or FI(60) in the long and short sides of the polarizer protective film are preferably 0.65 or less, 0.63 or less, 0.62 or less, 0.61 or less, and 0.6 or less, in that order, and preferably exceed the values ​​of FI(45) in the long and short sides. By setting FI(30) and FI(60) to the above ranges, color variations can be effectively suppressed over a wide area of ​​regions where color variations are likely to occur.

[0115] In the case of a light source using a metal fluorine compound activated with manganese ions, such as KSF, as a red phosphor, Rob(30) and / or Rob(60) of the polarizer protective film are preferably 6570 nm or higher or 6600 nm or higher. Rob(30) is further preferably 6960 nm or higher, 7150 nm or higher, 7340 nm or higher, and 7530 nm or higher, in that order. Rob(30) and / or Rob(60) are preferably less than Rob(45). Rob(30) and / or Rob(60) of the polarizer protective film are preferably 12200 nm or lower. Rob(30) and / or Rob(60) are further preferably 11900 nm or lower, 11700 nm or lower, 11500 nm or lower, and 11300 nm or lower, in that order. Rob(30) and / or Rob(60) are preferably greater than Rob(45).

[0116] In the case of a light source using a metal fluorine compound activated with manganese ions, such as KSF, as a red phosphor, it is preferable that the values ​​of Rob(30) and / or Rob(60) in the long and short sides of the polarizer protective film are 6600 nm or greater. Furthermore, the values ​​of Rob(30) and / or Rob(60) in the long and short sides are more preferably 6960 nm or greater, 7150 nm or greater, 7340 nm or greater, and 7530 nm or greater, in that order. It is also preferable that the values ​​of Rob(30) and / or Rob(60) in the long and short sides are less than the values ​​of Rob(45) in the long and short sides. It is preferable that the values ​​of Rob(30) and / or Rob(60) in the long and short sides of the polarizer protective film are 12200 nm or less. The values ​​of Rob(30) and / or Rob(60) in the long and short sides are preferably 11900nm or less, 11700nm or less, 11500nm or less, and 11300nm or less, in that order. Furthermore, it is preferable that the values ​​of Rob(30) and / or Rob(60) in the long and short sides exceed the values ​​of Rob(45) in the long and short sides.

[0117] The ratio of the difference between FI(30) and FI(60) (ΔFI = FI(60) - FI(30)) to FI(45) of the polarizer protective film (ΔFI / FI(45)) is preferably 0.2 or more and 0.35 or less. It is preferable that the ΔFI / FI(45) values ​​for the polarizer protective film in the long-side and short-side directions are 0.2 or more and 0.35 or less. ΔFI / FI(45) is further preferred in the order of 0.22 or higher, 0.23 or higher, 0.24 or higher, and 0.25 or higher. ΔFI / FI(45) is further preferred in the order of 0.34 or lower, 0.33 or lower, 0.32 or lower, and 0.31 or lower. The values ​​of ΔFI / FI(45) in the long and short sides are further preferably 0.22 or greater, 0.23 or greater, 0.24 or greater, and 0.25 or greater, in that order. The values ​​of ΔFI / FI(45) in the long and short sides are further preferably 0.34 or less, 0.33 or less, 0.32 or less, and 0.31 or less, in that order. By setting ΔFI / FI(45) to the above value or higher, color unevenness can be effectively suppressed over a wide area of ​​regions prone to color unevenness. Furthermore, a uniform color tone can be achieved across the entire screen. While ΔFI / FI(45) can be increased by improving the uniaxiality of the polarizer protective film, a value below the above is preferable due to factors such as tearing susceptibility and handling along the slow axis direction within the film surface.

[0118] In the case of a light source using a metal fluorine compound activated with manganese ions, such as KSF, as a red phosphor, the difference between Rob(30) and Rob(60) of the polarizer protective film (ΔRob = Rob(60) - Rob(30)) is preferably 1880 nm or more or 1900 nm or more, and more preferably in the order of 2000 nm or more, 2100 nm or more, 2200 nm or more, and 2250 nm or more. The ΔRob of the polarizer protective film is preferably 3400 nm or less or 3380 nm or less, and more preferably in the order of 3300 nm, 3200 nm or less, 3100 nm or less, 3000 nm or less, and 2900 nm or less. In the case of a light source using a metal fluorine compound activated with manganese ions, such as KSF, as a red phosphor, the values ​​of ΔRob in the long and short sides of the polarizer protective film are preferably 1900 nm or more, and more preferably 2000 nm or more, 2100 nm or more, 2200 nm or more, and 2250 nm or more in that order. The values ​​of ΔRob in the long and short sides of the polarizer protective film are preferably 3400 nm or less, and more preferably 3300 nm, 3200 nm or less, 3100 nm or less, 3000 nm or less, and 2900 nm or less in that order. The preferred range for ΔRob / Rob(45) is the same as the range for ΔFI / FI(45).

[0119] The surface roughness (SRa) (JIS B0601:1994) of the high-Re polarizer protective film is preferably 0.05 μm or less, more preferably 0.01 μm or less, and even more preferably 0.005 μm or less on at least one side, and more preferably both sides. By setting the SRa to 0.05 μm or less, a highly transparent film can be made. Furthermore, to ensure the slipperiness of the film, the SRa is preferably 0.0001 μm or more, and more preferably 0.0005 μm or more.

[0120] The ten-point average surface roughness (SRz) (JIS B0601:1994) of the high-Re polarizer protective film is preferably 1.0 μm or less, more preferably 0.70 μm or less, even more preferably 0.50 μm or less, particularly preferably 0.30 μm or less, and most preferably 0.2 μm or less on at least one side, and more preferably both sides. The SRz is preferably 0.001 μm or more, and even more preferably 0.005 μm or more.

[0121] It is preferable that the SRa and SRz values ​​on the light source side (opposite side from the liquid crystal cell) of the light source-side polarizing plate are within the above range. The phenomenon of increased surface roughness is often caused by coarse particles such as particle aggregates and catalyst residues. If these values ​​are below the above upper limit, it is possible to prevent coarse particles from falling off and scratching the film surface during the film manufacturing and processing processes, and after the film is incorporated as a liquid crystal display device, thereby suppressing the formation of bright spots and dark spots that degrade image quality. Furthermore, it is possible to suppress a decrease in image sharpness and contrast. Coarse particles in the film are preferably removed by methods such as removing them with a filter during resin manufacturing or by installing a filter in the film manufacturing line. Furthermore, if the surface is an easily adhering layer or other coating layer, it is preferable to filter the coating solution after preparation, or to install a filter in the line that sends the coating solution to the coating die and filter it.

[0122] It is preferable that the number of foreign particles with a major axis of 100 μm or more in the high-Re polarizer protective film be two or less. Foreign particles with a major axis of 100 μm or more in the high-Re polarizer protective film are those whose major axis is 100 μm or more when an inspection polarizer is placed on the high-Re polarizer protective film side of a polarizer plate cut to a size to be incorporated into an image display device, so as crossed nicols. Examples of foreign particles in the film include aggregates of lubricant particles. It is preferable not only to remove aggregates with a small pore size filter during film formation, but also to use lubricant particles only on the surface layer of the film in a multilayer structure. It is also preferable to not use lubricant particles in the film, but to use lubricant particles in an easy-adhesion coating on the surface.

[0123] Furthermore, degraded resin can also become foreign matter in the film. While hard foreign matter in the molten resin can be removed by the aforementioned filter, gel-like foreign matter resulting from thermal degradation of the molten resin can deform to some extent at the molten resin temperature, and may pass through the filter even if it is larger than the filter's pore size. In the case of large thermally degraded material, it may be cut by the filter, actually increasing the number of foreign objects. Also, thermally degraded resin generated in the line after the filter will remain in the film. These foreign objects not only fail to follow the stretch orientation of the surrounding resin during the stretching process, but also disrupt the stretch orientation of the surrounding resin, appearing as bright spots when measured with crossed nicols. Moreover, even small, hard foreign objects that pass through the filter may form voids between them and the resin during stretching, becoming foreign matter in the film. Furthermore, the filter's pore size does not mean that only foreign matter larger than the pore size can pass through; a certain proportion of foreign matter larger than the pore size will pass through. It is more preferable that the number of foreign particles with a major axis of 100 μm or more in the high-Re polarizer protective film be one or less, and it is preferable that there be zero, i.e., none.

[0124] Furthermore, the number of foreign particles with a major axis of 50 μm or more in the high-Re polarizer protective film is preferably 5 or less, more preferably 3 or less, even more preferably 1 or less, and particularly preferably 0. Furthermore, the number of foreign particles with a major axis of 20 μm or more in the high Re polarizer protective film is preferably 10 or less, more preferably 5 or less, even more preferably 3 or less, particularly preferably 1 or less, and most preferably 0.

[0125] If such foreign matter is present in a high-reactive-index polarizer protective film, colored foreign matter may be visible when viewing the image up close. Even if the foreign matter is nearly colorless and transparent, it may cause slight color differences or disruptions in color uniformity in minute areas, possibly due to a difference in refractive index compared to the surrounding normal areas. In the case of a light source-side polarizer, it may result in dark spots.

[0126] To reduce the foreign matter in the film, it is preferable to minimize the areas where the molten resin accumulates in the path through which it passes. Specifically, in an extruder, it is preferable to minimize the steps between screw elements, between blocks of the barrel, and at each connection point of the piping. Furthermore, it is preferable to design piping, filter housings and filter elements, and nozzle passages to minimize resin accumulation, and to reduce the roughness of the inner walls of these components.

[0127] Furthermore, the amount of foreign matter tends to increase at the start of film production or when the resin extrusion rate is increased. In these cases, it is preferable to temporarily increase the resin extrusion rate and then reduce it back to the specified amount.

[0128] Furthermore, it is preferable to take measures such as conducting defect inspections after film formation and not using films with a large amount of foreign matter in the manufacture of polarizing plates, and marking defective areas and not using polarizing plates from those areas.

[0129] The haze of the high-Re polarizer protective film is preferably 5% or less, more preferably 3% or less, even more preferably 2% or less, and particularly preferably 1.5% or less. The lower limit of the haze is preferably 0.01% or more, and even more preferably 0.1% or more. Note that SRa and SRz are the values ​​of the surface of the high-Re polarizer protective film of the raw material before the application of functional layers such as the low-reflection layer described later. However, if an easy-adhesion layer is provided inline, the values ​​of the easy-adhesion layer surface shall be used. The same applies to haze. Haze can be measured in accordance with JIS-K7105 using a turbidimeter (NHD2000, manufactured by Nippon Denshoku Industries).

[0130] The resin used in the high-Re polarizer protective film is not particularly limited as long as it produces birefringence due to orientation, but polyester, polycarbonate, and polystyrene are preferred, with polyester being particularly preferred, due to their ability to increase retardation and their low moisture permeability and hygroscopicity. Preferred polyesters include polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), polytetramethylene terephthalate (PBT), and polyethylene naphthalate (PEN), with PET or PEN being preferred among them. These polyesters may have copolymerized carboxylic acid components and / or glycol components other than the main components, but when the total amount of carboxylic acid components and / or glycol components is 100 mol%, the total amount of carboxylic acid components and / or glycol components other than the main components is preferably 10 mol% or less, more preferably 5 mol% or less, even more preferably 2 mol% or less, particularly preferably 1.5 mol% or less, and most preferably 1.2 mol% or less. Below these levels, heat resistance can be increased and the thermal shrinkage rate can be reduced. Note that the glycol components other than the main components include by-products such as diethylene glycol. Furthermore, since side reactions such as glycol dimerization cannot be completely avoided during polyester polymerization, the amount of glycol components other than the main components is preferably 0.1 mol% or more. The most preferable range for the amount of glycol components other than the main components is 0.2 to 1 mol%. The above-mentioned polyester is easy to handle because it is easily stretched to a high magnification and has impact resistance, and because it has low moisture permeability and low moisture absorption, it reduces warping of liquid crystal cells due to environmental changes. Polyester high-Re polarizer protective films are suitable for use in large liquid crystal display devices such as 45-inch (diagonal length of screen is 45 inches) or larger, 50-inch (diagonal length of screen is 50 inches) or larger, 55-inch (diagonal length of screen is 55 inches) or larger, and 60-inch (diagonal length of screen is 60 inches) or larger.

[0131] The thickness of the high-Re polarizer protective film is preferably 25 to 120 μm, however, since retardation is the product of the refractive index in the plane of the film and its thickness, the appropriate thickness range will vary depending on the resin, stretching ratio, etc. For example, for polyethylene terephthalate, a thickness of 60 μm or more is preferable, and more preferably 63 μm or more, 65 μm or more, 70 μm or more, 73 μm or more, and 75 μm or more, in that order. Also, a thickness of 100 μm or less is preferable, and more preferably 95 μm or less, 90 μm or less, 87 μm or less, 85 μm or less, and 83 μm or less, in that order. A thickness below the above limits is suitable for thinning image display devices. Furthermore, if polyethylene naphthalate is used, a particle size of 25 μm or more is preferred, followed in order of preference by 30 μm or more, 35 μm or more, and 37 μm or more, and also preferred to be 60 μm or less, followed in order of preference by 55 μm or less, 50 μm or less, and 47 μm or less. These upper and lower limits are combined in a range of thickness when the stretching ratio is low, and in a range of thickness when the stretching ratio is high. The variation in the thickness of the high-Re polarizer protective film is preferably 6% or less, more preferably 5% or less, even more preferably 4% or less, and particularly preferably 3% or less, in both the MD and TD directions.

[0132] The intrinsic viscosity (IV) of the resin constituting the film is preferably 0.45 to 1.5 dL / g. In the case of PET, the IV is preferably 0.5 to 1.5 dL / g. The lower limit of the IV is more preferably 0.53 dL / g, and even more preferably 0.55 L / g. The upper limit of the IV is more preferably 1.2 dL / g, even more preferably 1 dL / g, and particularly preferably 0.8 dL / g. In the case of PEN, the lower limit of IV is preferably 0.45 dL / g, more preferably 0.48 dL / g, even more preferably 0.5 dL / g, and particularly preferably 0.53 dL / g. The upper limit of IV is more preferably 1 dL / g, more preferably 0.8 dL / g, even more preferably 0.75 dL / g, and particularly preferably 0.7 dL / g. By defining the above range, the film will have excellent mechanical strength, such as impact resistance, and can be manufactured efficiently without placing a heavy load on the equipment.

[0133] In the polarizer protective film, the amount of antimony atoms in the residue insoluble in the mixed solvent of parachlorophenol and tetrachloroethane is preferably 50 mg or less, more preferably 30 mg or less, even more preferably 20 mg or less, particularly preferably 10 mg or less, and most preferably 5 mg or less per 1 kg of resin constituting the film. A smaller amount of antimony atoms in the residue is preferable, but the lower limit is preferably 0.1 mg, more preferably greater than 0.5 mg, and even more preferably greater than 1 mg. The polarizer protective film is preferably formed from a resin polymerized using an antimony compound as a catalyst, particularly a polyester resin. Examples of antimony compounds used as catalysts include antimony trioxide, antimony pentoxide, antimony acetate, and antimony glycoside, with antimony trioxide (Sb2O3) being preferred. In addition to antimony compounds, titanium compound catalysts such as tetrabutoxytitanate, and aluminum-based catalysts such as basic aluminum acetate and hindered phenol-containing phosphate esters (e.g., Irganox 1222) may also be used as catalysts. Furthermore, it is preferable to add polymerization stabilizers, additives, and molten resistance modifiers. Typical examples include phosphorus compounds such as trimethyl phosphate and phosphoric acid, magnesium compounds such as magnesium acetate, and calcium compounds such as calcium acetate.

[0134] To keep the amount of antimony atoms in the residue insoluble in the mixed solvent of the film below the above limit, it is preferable to keep the amount of antimony atoms in the residue insoluble in the mixed solvent of the resin used in manufacturing the film below the above limit. Methods for reducing the amount of antimony atoms in the insoluble residue of the polyester resin to the above-mentioned level include, for example, the following methods, which can be used individually or in combination. The amount of antimony added to the polymerized polyester resin is preferably 300 ppm or less, more preferably 250 ppm or less, even more preferably 220 ppm or less, and particularly preferably 200 ppm or less, in terms of antimony atomic weight. The lower limit of the antimony amount is preferably 30 ppm, even more preferably 50 ppm, and especially preferably 80 ppm. The antimony compound is added as a solution or slurry of ethylene glycol. At this time, the concentration of the antimony compound is preferably 10% by mass or less, more preferably 7% by mass or less, and especially preferably 5% by mass or less. It is preferable to set the maximum polymerization temperature of the polyester resin to 290°C or lower, and more preferably to 285°C or lower. • Increase the degree of reduced pressure so that the time to reach the maximum polymerization temperature of the polyester resin is within 45 minutes, or even within 30 minutes. For continuous polymerization, this refers to the average residence time. When adding phosphorus, magnesium, or calcium compounds to the polymerized polyester resin, the amount added is preferably 15-120 ppm, more preferably 20-100 ppm, and even more preferably 25-80 ppm in terms of phosphorus atomic weight, and preferably 30-120 ppm, and more preferably 40-100 ppm, in terms of magnesium or calcium atomic weight. Furthermore, it is preferable to add the phosphorus compound after adding the magnesium or calcium compound, and to add it in multiple stages.

[0135] The high-Re polarizer protective film preferably has a light transmittance of 20% or less at a wavelength of 380 nm. More preferably, the light transmittance at 380 nm is 15% or less, even more preferably 10% or less, and particularly preferably 5% or less. If the light transmittance is 20% or less, the deterioration of iodine and dichroic dyes in the polarizing layer due to ultraviolet light can be suppressed. The transmittance is measured perpendicular to the plane of the film and can be measured using a spectrophotometer (for example, Hitachi U-3500).

[0136] Reducing the light transmittance of a high-Re polarizer protective film to 20% or less at a wavelength of 380 nm can be achieved by adding an ultraviolet absorber to the film, applying a coating solution containing an ultraviolet absorber to the film surface, or appropriately adjusting the type, concentration, and thickness of the ultraviolet absorber. The ultraviolet absorber is a known substance. Examples of ultraviolet absorbers include organic ultraviolet absorbers and inorganic ultraviolet absorbers, but organic ultraviolet absorbers are preferred from the viewpoint of transparency.

[0137] Examples of organic UV absorbers include benzotriazole-based, benzophenone-based, cyclic iminoester-based, and combinations thereof, but they are not particularly limited as long as they fall within the desired absorbance range.

[0138] Furthermore, it is preferable to add particles with an average particle size of 0.05 to 2 μm to the high-Re polarizer protective film to improve its slipperiness. Examples of particles include inorganic particles such as titanium dioxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, and calcium fluoride, as well as organic polymer particles such as styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and silicone-based particles. These particles may be added to the entire film, or they may be added only to the skin layer in a co-extruded multilayer skin-core structure. Alternatively, the film itself may not contain particles, and the particles may be added to the easy-adhesion layer described later. When adding particles to the resin of a film, there are methods such as using a raw material resin that has already been manufactured with added particles, or using a masterbatch in which particles have been added at a high concentration during film formation. In either method, if there are many particle aggregates, the clarity and contrast of the image may decrease, the surface roughness may increase, and particles may fall off. It is preferable to remove these particle aggregates using filters during the manufacturing of the raw material resin or masterbatch. Furthermore, it is preferable to install a filter in the molten resin line during film formation to remove particle aggregates. The filters used for these purposes preferably have a particle size of 50 μm or less with a 95% separation rate, more preferably 20 μm or less, particularly preferably 10 μm or less, and most preferably 5 μm or less. Furthermore, while catalysts for polymerizing resins (especially polyester resins) include antimony compounds such as antimony trioxide, titanium compounds such as tetrabutyl titanate, aluminum compounds such as basic aluminum acetate, and mixed catalysts of esters or salts of 3,5-di-tert-butyl-4-hydroxybenzylphosphonic acid such as Irganox 1222 and Irganox 1425, these catalyst residues can also lead to haze reduction and increased surface roughness. It is preferable to use resins manufactured by selecting catalyst amounts and polymerization conditions that minimize residue generation, tailored to each catalyst. In addition, it is preferable to install a filter with the above-mentioned pore size in the molten resin line during film formation. Preferred examples of filters include sintered metal, sintered metal wire, metal mesh, and ceramic.

[0139] High-Re polarizer protective films can be obtained according to general film manufacturing methods. The explanation will use the case where the film is a polyester film as an example. In the following description of the manufacturing method, the high-Re polarizer protective film may sometimes be referred to as a polyester film. For example, a method for manufacturing polyester film involves melting polyester resin (e.g., PET), extruding it into a sheet, stretching the unoriented polyester in the longitudinal or transverse direction at a temperature above the glass transition temperature, and then subjecting it to heat treatment.

[0140] The polarizer protective film may be uniaxially oriented or biaxially oriented, but if the biaxiality is strong, a thicker film is required to ensure the necessary Rob(45). Even if Rob(45) can be brought within an appropriate range by adjusting the thickness, uniaxial oriented is preferable because it is easier to bring Rob(30) and Rob(60) within an appropriate range, as well as ΔFI / FI(45) within an appropriate range. Furthermore, even if biaxially oriented, a high degree of uniaxiality is preferable.

[0141] The main orientation axis of the polarizer protective film may be the direction in which the film runs (sometimes called the longitudinal direction or MD direction) or a direction perpendicular to the longitudinal direction (sometimes called the orthogonal direction or TD direction). Roll stretching is preferred for MD stretching, and tenter stretching is preferred for TD stretching. Tenter stretching is the preferred method in terms of the low number of scratches on the film surface, productivity, and lamination with a polarizer stretched from PVA.

[0142] In stretching, the unstretched film is preheated and stretched, preferably at 80-130°C, more preferably at 90-120°C. The stretching ratio is preferably 3.6-7 times in the main stretching direction, more preferably 3.8-6.5 times, even more preferably 4-6.2 times, and particularly preferably 4.1-6 times. Lower stretching temperatures and higher stretching ratios tend to increase Rob(45) and decrease ΔFI / FI(45). Furthermore, to further enhance uniaxiality, it is preferable to shrink the material in a direction perpendicular to the stretching direction during stretching. In the case of TD stretching with a tenter, shrinkage can be achieved, for example, by narrowing the tenter clip spacing. The shrinkage treatment is preferably 1-20%, and more preferably 2-15%.

[0143] When performing biaxial stretching, in order to set Rob(45), Rob(30), Rob(60), and ΔFI / FI(45) within the appropriate range, the above is used as the main stretching, and it is preferable to stretch by 1.2 times or less in a direction perpendicular to the main stretching before the main stretching, and more preferably by 1.15 times or less, and particularly preferably by 1.13 times or less. The lower limit of the stretching ratio in the perpendicular direction is preferably 1.01 times, more preferably 1.03 times, and particularly preferably 1.05 times.

[0144] It is preferable to perform heat setting after stretching. The heat setting temperature is preferably 150 to 230°C, and more preferably 170 to 220°C. Lower heat setting temperatures tend to increase Rob(45) and decrease ΔFI / FI(45). However, lower heat setting temperatures tend to result in a higher thermal shrinkage rate of the film. In thermal setting, it is also preferable to perform a relaxation treatment in the main stretching direction or in a direction perpendicular thereto. The relaxation treatment is preferably 0.5 to 10%, and more preferably 1 to 5%.

[0145] After heat setting, the film is cooled and then wound up. During the cooling process, it is preferable to perform additional micro-stretching in the main stretching direction to impart appropriate thermal shrinkage force, thereby reducing warping of the liquid crystal panel after assembly. The additional micro-stretching is preferably performed when the film temperature is between 80 and 150°C, with a magnification of 1 to 5%, and more preferably 1.5 to 3%. Additionally, annealing may be performed after film formation to adjust the thermal shrinkage rate.

[0146] High-Re polarizer protective films may be subjected to treatments that improve adhesion, such as corona treatment, flame treatment, or plasma treatment.

[0147] Since retardation from an oblique direction is affected by the film thickness, it is preferable to reduce variations in film thickness. To reduce thickness variations in the TD direction of the film, it is preferable to employ methods such as precisely controlling the spacing of the nozzle tips when extruding the molten resin into a sheet, optimizing the internal flow path of the nozzle so that the resin is extruded uniformly in the width direction from the nozzle tip, and reducing the temperature difference in the width direction at the nozzle tip. It is also preferable to measure the thickness of the film in the TD direction and to create a control program that feeds the result back into the spacing of the nozzle tips so that the fluctuations are gradual. To reduce thickness variations in the film in the MD direction, it is preferable to suppress the pulsation of the extruded resin, improve the vibration damping of casting equipment such as die caps and cooling rolls, and reduce fluctuations in the air pressure used for pinning or, in the case of electrostatic application, reduce the vibration of the electrodes to keep the contact point of the sheet-like extruded resin with the cooling roll constant. It is preferable to implement these measures in combination.

[0148] Furthermore, temperature fluctuations during tenter stretching can alter the orientation of the film, affecting diagonal retardation. Temperature differences are particularly likely to occur near the clips due to the clip temperature. Additionally, the forces acting on the film may differ due to the Boeing effect. These factors are thought to cause differences in the optical properties of the film in the TD direction. Taking these factors into consideration, it is preferable to ensure uniform optical properties in the TD direction of the film after tenter stretching and before slitting by taking the necessary time during preheating to ensure uniform film temperature in the width direction, varying the shape and size of the tenter's hot and cooling air outlets in the width direction, varying the air velocity in the width direction, and providing auxiliary heating means at the edges. It is also preferable to minimize temperature fluctuations in the tenter to reduce fluctuations in the MD direction. In this invention, it is possible to slit and use only the portion of the manufactured long film whose optical properties fall within the aforementioned range, for example, the central portion. However, from an economic standpoint, it is preferable that the portion removed by slitting be narrow, and furthermore, it is preferable to manufacture a wide film and then slit it to obtain multiple films. To achieve this, it is preferable to adjust the stretching conditions during tenter stretching in film manufacturing so that the optical properties become uniform in the width direction of the film. Since retardation from an oblique direction tends to increase due to variations in orientation state in addition to variations in film thickness, it is preferable to control both with high precision.

[0149] (Easy adhesion layer) The high-Re polarizer protective film may be provided with an easy-adhesion layer (easy-adhesion layer P1) to improve adhesion to the polarizer and adhesion to the orientation layer. The resin used in the easy-adhesion layer can be polyester resin, polyurethane resin, polycarbonate resin, or acrylic resin, with polyester resin, polyester polyurethane resin, polycarbonate polyurethane resin, or acrylic resin being preferred. The easy-adhesion layer is preferably crosslinked. Examples of crosslinking agents include isocyanate compounds, melamine compounds, epoxy resins, and oxazoline compounds. Adding a water-soluble resin such as polyvinyl alcohol is also a useful means of improving adhesion to the polarizer.

[0150] The easy-adhesion layer can be formed by applying and drying a water-based paint, which contains these resins and, if necessary, crosslinking agents, particles, etc., to the high-Re polarizer protective film. Examples of particles include those used in the aforementioned substrate. The easy-adhesion layer may be applied offline to the stretched film, but it is preferable to apply it in-line during the film-forming process. When applied in-line, it may be applied either before longitudinal stretching or transverse stretching, but it is preferable to apply it immediately before transverse stretching and then dry and crosslink it in a tenter preheating, heating, heat treatment process. When in-line coating is applied immediately before longitudinal stretching by rolls, it is preferable to dry the film in a vertical dryer after coating before guiding it to the stretching rolls. The coating amount of the easy-adhesion layer (coating amount after drying) is 0.01 to 1 g / m². 2 Preferably, 0.03~0.5g / m 2 It is preferable. In the coating of easily adhering layers, if there are many aggregates of particles in the coating solution, the haze may decrease or the surface roughness may increase. It is preferable to install filters in the line that supplies the coating solution to the coating die and in the coating solution circulation line to remove the aggregates of particles. The filters used should preferably have a particle size of 10 μm or less with 95% separation, more preferably 5 μm or less, and particularly preferably 2 μm or less. Preferred filters include cartridge filters and bag filters.

[0151] When a film has an easy-adhesion layer, interference occurs between the reflected light at the interface between the easy-adhesion layer and the film substrate and the reflected light at the interface on the opposite side of the easy-adhesion layer from the film substrate (for example, the interface with the functional layer, adhesive layer, or tack layer). This interference color may occur in areas where the thickness of the easy-adhesion layer is uneven. This interference color is noticeable in black display areas or when the power is turned off. To suppress this interference color, it is preferable to reduce the interference.

[0152] To reduce interference, it is preferable to bring the refractive index of the easy-adhesion layer close to that of the film base. In the present invention, the film base may have birefringence, but when the refractive index in the phase-advancing axis direction of the film base is nf and the refractive index in the phase-lagging axis direction is nl, the refractive index n of the easy-adhesion layer is preferably nf-0.05≦n≦nl+0.05, more preferably nf-0.02≦n≦nl+0.02, and even more preferably nf≦n≦nl.

[0153] For example, if the film base is polyethylene terephthalate, the refractive index in the phase-advancing axis direction is approximately 1.6 and the refractive index in the phase-lagging axis direction is approximately 1.7. Therefore, the lower limit of the refractive index of the easy-adhesion layer is preferably 1.55, more preferably 1.57, more preferably 1.58, even more preferably 1.59, and particularly preferably 1.6. The upper limit of the refractive index of the easy-adhesion layer is preferably 1.75, more preferably 1.73, more preferably 1.72, even more preferably 1.71, and particularly preferably 1.7.

[0154] The refractive index of the easy-adhesion layer may exhibit birefringence when stretched after coating as an in-line coat. In that case, the refractive index of the easy-adhesion layer is the average refractive index in the phase-advancing axis direction and the phase-lagging axis direction. The refractive index of the easy-adhesion layer can be measured, for example, by applying the coating solution of the easy-adhesion layer to a glass plate or the like and drying it, then measuring it with an ellipsometer or the like.

[0155] To achieve the above refractive index range, methods such as adjusting the refractive index of the resin used in the easy-adhesion layer or adding high refractive index particles are preferred. If a resin is used, the refractive index can be increased by aromatic components, so it is preferable to use a resin having a benzene ring or a naphthalene ring in the main chain or side chain, and especially a resin having a naphthalene ring. Specifically, polyester copolymerized with naphthalenedicarboxylic acid is preferred. Polyester copolymerized with naphthalenedicarboxylic acid may be used in blend with other resins as needed. It may also be used as a polyester polyol for polyester polyurethane. The naphthalenedicarboxylic acid component in the polyester is preferably 30 to 90 mol%, and more preferably 40 to 80 mol%, when the total acid component is considered to be 100 mol%.

[0156] The lower limit of the refractive index of the high refractive index particles is preferably 1.7, more preferably 1.75. The upper limit of the refractive index of the high refractive index particles is preferably 3, more preferably 2.7, and even more preferably 2.5. As high refractive index particles, particles containing metal oxides with a high refractive index are preferred. Examples of such metal oxides include TiO2 (refractive index 2.7), ZnO (refractive index 2.0), Sb2O3 (refractive index 1.9), SnO2 (refractive index 2.1), ZrO2 (refractive index 2.4), Nb2O5 (refractive index 2.3), CeO2 (refractive index 2.2), Ta2O5 (refractive index 2.1), Y2O3 (refractive index 1.8), La2O3 (refractive index 1.9), In2O3 (refractive index 2.0), Cr2O3 (refractive index 2.5), and composite oxides containing these metal atoms. Among these, SnO2 particles, TiO2 particles, ZrO2 particles, and TiO2-ZrO2 composite particles are preferred.

[0157] The average particle size of the high refractive index particles is preferably 5 nm or larger, more preferably 10 nm or larger, even more preferably 15 nm or larger, and particularly preferably 20 nm or larger. An average particle size of 5 nm or larger is preferable because it makes aggregation less likely.

[0158] The average particle size of the high refractive index particles is preferably 200 nm or less, more preferably 150 nm or less, even more preferably 100 nm or less, and particularly preferably 60 nm or less. An average particle size of 200 nm or less is preferable for good transparency.

[0159] The content of high refractive index particles in the easy-adhesion layer is preferably 2% by mass or more, more preferably 3% by mass or more, even more preferably 4% by mass or more, and particularly preferably 5% by mass or more. A content of 2% by mass or more of high refractive index particles in the easy-adhesion layer is preferable because it allows for a high refractive index to be maintained in the easy-adhesion layer, effectively achieving low coherence.

[0160] The content of high refractive index particles in the easy-adhesion layer is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, and particularly preferably 20% by mass or less. A content of 50% by mass or less of high refractive index particles in the easy-adhesion layer is preferable because it maintains film-forming properties.

[0161] It is preferable that an easy-adhesion layer containing high refractive index particles is laminated on at least one side of the polarizer protective film, and furthermore, it is preferable that the viewing-side polarizer protective film of the viewing-side polarizer plate has an easy-adhesion layer containing high refractive index particles, and in particular, it is preferable that the viewing-side surface of the polarizer protective film has an easy-adhesion layer containing high refractive index particles.

[0162] (Functional layer) When a high-reactivity polarizer protective film is used as a polarizer on the viewing side, it is also preferable that a functional layer such as a hard coat layer, anti-reflective layer, low-reflection layer, anti-glare layer, or anti-static layer is provided on the side of the high-reactivity polarizer protective film opposite to the side on which the polarizer is laminated. In particular, the high-reactivity polarizer protective film is often the outermost surface on the viewing side of a liquid crystal display device, and it is preferable that at least one of the anti-reflective layer, low-reflection layer, or anti-glare layer is provided. The anti-reflective layer, low-reflection layer, and anti-glare layer are collectively called a reflection reduction layer. The reflection reduction layer not only prevents external light from reflecting onto the liquid crystal display screen and making it difficult to see, but also suppresses reflection at the interface, reducing iridescence and making it less noticeable. Furthermore, in a high-reactivity polarizer protective film with a functional layer, the film in the state before the functional layer is provided is called the base film. The base film may also include the above-mentioned easy-adhesion layer.

[0163] The upper limit of the reflectivity of the high-Re polarizer protective film, measured from the reflection reduction layer side, is preferably 5%, more preferably 4%, even more preferably 3%, particularly preferably 2%, and most preferably 1.5%. Below the above upper limit, the reflection of ambient light can be reduced, improving the visibility of the screen. The lower limit of the reflectivity is not particularly limited, but from a practical standpoint, it is preferably 0.01%, and even more preferably 0.1%. There are various types of anti-reflective layers, including low-reflection layers, anti-reflective layers, and anti-glare layers.

[0164] (Low reflective layer) A low-reflectance layer is typically a low-refractive-index layer, which, when applied to the surface of a substrate film, reduces the refractive index difference with air, thereby lowering the reflectivity.

[0165] (Anti-reflection layer) The anti-reflective layer is a layer that controls reflection by interfering with reflected light at the interface by controlling the thickness of the low refractive index layer. Preferably, the thickness of the low refractive index layer is approximately the wavelength of visible light (400-700 nm) / (refractive index of the low refractive index layer × 4). It is also preferable to provide a high refractive index layer between the anti-reflective layer and the base film. Two or more layers, including a low refractive index layer and / or a high refractive index layer, may be provided to further enhance the anti-reflective effect through multiple interference. The high refractive index layer and the low refractive index layer together are sometimes referred to as the anti-reflective layer.

[0166] In the case of an anti-reflective layer, the upper limit of the reflectance is preferably 2%, more preferably 1.5%, even more preferably 1.2%, and particularly preferably 1%.

[0167] (Low refractive index layer) The refractive index of the low refractive index layer is preferably 1.45 or less, and more preferably 1.42 or less. Furthermore, the refractive index of the low refractive index layer is preferably 1.2 or more, and more preferably 1.25 or more. Note that the refractive index of the low refractive index layer is the value measured under the condition of a wavelength of 589 nm.

[0168] The thickness of the low refractive index layer is not limited, but it can usually be set appropriately within the range of approximately 30 nm to 1 μm. When used as an anti-reflective layer, the thickness of the low refractive index layer is preferably 70 to 120 nm, and more preferably 75 to 110 nm.

[0169] Examples of low refractive index layers include (1) a layer made of a resin composition containing a binder resin and low refractive index particles, (2) a layer made of a fluororesin which is a low refractive index resin, (3) a layer made of a fluororesin composition containing silica or magnesium fluoride, and (4) a thin film of a low refractive index substance such as silica or magnesium fluoride.

[0170] The binder resin contained in the resin composition of (1) can be polyester, polyurethane, polyamide, polycarbonate, acrylic, etc., without any particular limitations. Among these, acrylic is preferred, and it is preferable that it is obtained by polymerizing (crosslinking) a photopolymerizable compound by light irradiation.

[0171] Examples of photopolymerizable compounds include photopolymerizable monomers, photopolymerizable oligomers, and photopolymerizable polymers, which can be used after being appropriately adjusted. A combination of a photopolymerizable monomer and a photopolymerizable oligomer or photopolymer is preferred as the photopolymerizable compound. These photopolymerizable monomers, photopolymerizable oligomers, and photopolymerizable polymers are preferably polyfunctional.

[0172] Examples of polyfunctional monomers include pentaerythritol triacrylate (PETA), dipentaerythritol hexaacrylate (DPHA), pentaerythritol tetraacrylate (PETTA), and dipentaerythritol pentaacrylate (DPPA). Monofunctional monomers may also be used in combination to adjust coating viscosity and hardness.

[0173] Examples of polyfunctional oligomers include polyester (meth)acrylate, urethane (meth)acrylate, polyester-urethane (meth)acrylate, polyether (meth)acrylate, polyol (meth)acrylate, melamine (meth)acrylate, isocyanurate (meth)acrylate, epoxy (meth)acrylate, and the like.

[0174] Examples of polyfunctional polymers include urethane (meth)acrylate, isocyanurate (meth)acrylate, polyester-urethane (meth)acrylate, and epoxy (meth)acrylate.

[0175] In addition to the above components, the coating agent may also contain polymerization initiators, crosslinking catalysts, polymerization inhibitors, antioxidants, UV absorbers, leveling agents, surfactants, and the like.

[0176] Examples of low refractive index particles included in the resin composition of (1) include silica particles (e.g., hollow silica particles) and magnesium fluoride particles, with hollow silica particles being preferred. Such hollow silica particles can be produced, for example, by the manufacturing method described in the examples of Japanese Patent Application Publication No. 2005-099778.

[0177] The average particle diameter of the primary particles of the low refractive index particles is preferably 5 to 200 nm, more preferably 5 to 100 nm, and even more preferably 10 to 80 nm. Low refractive index particles are more preferably surface-treated with a silane coupling agent, and more preferably surface-treated with a silane coupling agent having a (meth)acryloyl group. .

[0178] The content of low refractive index particles in the low refractive index layer is preferably 10 to 250 parts by mass, more preferably 50 to 200 parts by mass, and even more preferably 100 to 180 parts by mass, per 100 parts by mass of binder resin.

[0179] (2) As the fluororesin, a polymerizable compound or polymer thereof containing at least a fluorine atom in its molecule can be used. The polymerizable compound is not particularly limited, but those having curing reactive groups such as photopolymerizable functional groups and thermosetting polar groups are preferred. Compounds having multiple curing reactive groups simultaneously are also acceptable. The polymer of this polymerizable compound does not have the above-mentioned curing reactive groups, etc.

[0180] As compounds having photopolymerizable functional groups, for example, fluorine-containing monomers having ethylenically unsaturated bonds can be widely used.

[0181] To improve fingerprint resistance, it is also preferable to appropriately add known polysiloxane-based or fluorine-based antifouling agents to the low refractive index layer.

[0182] The surface of the low refractive index layer may be uneven to provide anti-glare properties, but a smooth surface is also preferable. When the surface of the low refractive index layer is a smooth surface, the arithmetic mean roughness SRa (JIS B0601:1994) of the surface of the low refractive index layer is preferably 20 nm or less, more preferably 15 nm or less, still more preferably 10 nm or less, and particularly preferably 1 to 8 nm. Also, the ten-point mean roughness Rz (JIS B0601:1994) of the surface of the low refractive index layer is preferably 160 nm or less, more preferably 50 to 155 nm.

[0183] (High refractive index layer) The refractive index of the high refractive index layer is preferably 1.55 to 1.85, more preferably 1.56 to 1.7. Note that the refractive index of the high refractive index layer is a value measured under the condition of a wavelength of 589 nm.

[0184] The thickness of the high refractive index layer is preferably 30 to 200 nm, more preferably 50 to 180 nm. The high refractive index layer may be a plurality of layers, but preferably 2 layers or less, and more preferably a single layer. In the case of a plurality of layers, it is preferable that the total thickness of the plurality of layers is within the above range.

[0185] When the high refractive index layer is two layers, it is preferable to make the refractive index of the high refractive index layer on the low refractive index layer side higher. Specifically, the refractive index of the high refractive index layer on the low refractive index layer side is preferably 1.6 to 1.85, and the refractive index of the other high refractive index layer is preferably 1.55 to 1.7.

[0186] The high refractive index layer preferably consists of a resin composition containing high refractive index particles and a resin. Among them, as the high refractive index particles, antimony pentoxide particles, zinc oxide particles, titanium oxide particles, cerium oxide particles, tin-doped indium oxide particles, antimony-doped tin oxide particles, yttrium oxide particles, and zirconium oxide particles are preferable. Among these, titanium oxide particles and zirconium oxide particles are suitable.

[0187] Two or more types of high refractive index particles may be used in combination. In particular, adding a first high refractive index particle and a second high refractive index particle with a lower surface charge is preferable to prevent aggregation.

[0188] The resins used in the high refractive index layer are the same as those listed for the low refractive index layer, with the exception of fluororesins.

[0189] In order to make the low refractive index layer, which is provided on top of the high refractive index layer, flat, it is preferable that the surface of the high refractive index layer is also flat. The method for making the surface of the low refractive index layer flat described above is used as a method for making the surface of the high refractive index layer flat.

[0190] The average particle diameter of the low refractive index particles and the primary particles of the low refractive index particles is preferably 5 to 200 nm, more preferably 5 to 100 nm, and even more preferably 10 to 80 nm. These particles are more preferably surface-treated, more preferably surface-treated with a silane coupling agent, and most preferably surface-treated with a silane coupling agent having a (meth)acryloyl group.

[0191] The content of low refractive index particles in the low refractive index layer is preferably 10 to 250 parts by mass, more preferably 50 to 200 parts by mass, and even more preferably 100 to 180 parts by mass, per 100 parts by mass of binder resin.

[0192] The content of low refractive index particles and high refractive index particles in each layer is preferably 10 to 400 parts by mass, more preferably 30 to 250 parts by mass, even more preferably 50 to 200 parts by mass, and particularly preferably 80 to 180 parts by mass, per 100 parts by mass of resin.

[0193] High refractive index layers and low refractive index layers can be formed, for example, by applying a resin composition containing a photopolymerizable compound to a substrate film, drying it, and then irradiating the resin composition in the form of a coating with light such as ultraviolet light to polymerize (crosslink) the photopolymerizable compound.

[0194] The resin compositions for the high refractive index layer and the low refractive index layer may optionally contain thermoplastic resins, thermosetting resins, solvents, polymerization initiators, dispersants, surfactants, antistatic agents, silane coupling agents, thickeners, color inhibitors, colorants (pigments, dyes), defoamers, leveling agents, flame retardants, UV absorbers, adhesion promoters, polymerization inhibitors, antioxidants, surface modifiers, lubrication agents, etc.

[0195] (Anti-glare layer) An anti-glare layer is a layer that reduces glare by creating irregularities on its surface to cause diffuse reflection, thereby preventing the reflection of the light source's shape when external light is reflected off the surface.

[0196] The arithmetic mean roughness (SRa) of the surface irregularities of the anti-glare layer is preferably 0.02 to 0.25 μm, more preferably 0.02 to 0.15 μm, and even more preferably 0.02 to 0.12 μm.

[0197] The ten-point average roughness (Rzjis) of the surface irregularities of the anti-glare layer is preferably 0.15 to 2 μm, more preferably 0.20 to 1.2 μm, and even more preferably 0.3 to 0.8 μm.

[0198] SRa and Rzjis are calculated from the roughness curve measured using a contact-type roughness meter in accordance with JIS B0601-1994 or JIS B0601-2001.

[0199] Examples of methods for providing an anti-glare layer to a base film include the following: • Apply a paint containing particles (fillers), etc., for anti-glare purposes. The anti-glare layer resin is cured while in contact with a mold having an uneven structure. • The anti-glare layer resin is applied to a mold having an uneven structure and then transferred to a base film. • Apply paints that undergo spinodal decomposition during drying and film formation.

[0200] The lower limit of the thickness of the antiglare layer is preferably 0.1 μm, more preferably 0.5 μm. The upper limit of the thickness of the antiglare layer is preferably 100 μm, more preferably 50 μm, and even more preferably 20 μm.

[0201] The refractive index of the antiglare layer is preferably 1.20 to 1.80, more preferably 1.40 to 1.70. Note that the refractive index of the antiglare layer is a value measured under the condition of a wavelength of 589 nm. It is also possible to provide irregularities on the low refractive index layer to form an antiglare low reflection layer, or to make the surface of the hard coat layer or the high refractive index layer irregular, and then provide a low refractive index layer thereon to provide an antireflection function, thereby forming an antiglare antireflection layer.

[0202] (Hard coat layer) It is also a preferred embodiment to provide a hard coat layer as the lower layer of the above reflection reducing layer. The pencil hardness of the hard coat layer is preferably H or more, more preferably 2H or more. The hard coat layer can be provided, for example, by applying and curing a composition solution of a thermosetting resin or a radiation curable resin.

[0203] Examples of the thermosetting resin include acrylic resin, urethane resin, phenol resin, urea melamine resin, epoxy resin, unsaturated polyester resin, silicone resin, and combinations thereof. A curing agent is added to these curable resins in the thermosetting resin composition as necessary.

[0204] Radiation-curable resins are preferably compounds having radiation-curable functional groups. Examples of radiation-curable functional groups include ethylenically unsaturated bonding groups such as (meth)acryloyl groups, vinyl groups, and allyl groups, as well as epoxy groups and oxetanyl groups. Of these, ionizing radiation-curable compounds are preferably compounds having ethylenically unsaturated bonding groups, more preferably compounds having two or more ethylenically unsaturated bonding groups, and even more preferably polyfunctional (meth)acrylate compounds having two or more ethylenically unsaturated bonding groups. Polyfunctional (meth)acrylate compounds may be monomers, oligomers, or polymers.

[0205] Specific examples of these include the binder resins mentioned above. To achieve the hardness required for a hard coat, it is preferable that the compound having radiation-curable functional groups contains 50% or more by mass of two- or more functional monomers, and more preferably 70% or more by mass. Furthermore, it is preferable that the compound having radiation-curable functional groups contains 50% or more by mass of three- or more functional monomers, and more preferably 70% or more by mass. The above-mentioned compounds having radiation-curable functional groups can be used individually or in combination of two or more.

[0206] The thickness of the hard coat layer is preferably in the range of 0.1 to 100 μm, and more preferably in the range of 0.8 to 20 μm.

[0207] The refractive index of the hard coat layer is more preferably 1.45 to 1.7, and even more preferably 1.5 to 1.6. Note that the refractive index of the hard coat layer is the value measured under conditions of a wavelength of 589 nm.

[0208] Methods for adjusting the refractive index of the hard coat layer include adjusting the refractive index of the resin, and, if particles are added, adjusting the refractive index of the particles. Examples of particles include those used in the anti-glare layer. In this invention, the hard coat layer may also be referred to as the reflection reduction layer.

[0209] When a functional layer is provided, an easy-adhesion layer (easy-adhesion layer P2) may be provided between it and the substrate. The easy-adhesion layer P2 preferably uses the resins, crosslinking agents, etc., mentioned above for easy-adhesion layer P1. Furthermore, easy-adhesion layer P1 and easy-adhesion layer P2 may have the same composition or different compositions. It is also preferable to provide the easy-adhesion layer P2 in-line. The easy-adhesion layer P1 and the easy-adhesion layer P2 may be coated and dried sequentially, but simultaneous coating of both sides is also a preferred configuration.

[0210] When a high-Re polarizer protective film is used as the polarizer plate on the light source side, the above-mentioned functional layer is not necessarily required, but it may be laminated. In particular, it is preferable to provide a hard coat layer on the side opposite to the surface on which the polarizer is laminated in order to prevent scratches caused by contact with the diffuser plate, prism plate, lens plate, reflective polarizer plate, etc. of the light source unit. It is also preferable to provide a reflection reduction layer or an anti-reflection layer, as this allows light from the light source to be transmitted more efficiently and reduces reflectivity, thereby further suppressing color unevenness. It is preferable that the reflection reduction layer or anti-reflection layer be provided on the side opposite to the surface on which the polarizer is laminated. When a high-Re polarizer protective film is used on the light source side polarizer plate, and the above-mentioned functional layer is provided on the side of the high-Re polarizer protective film opposite to the side on which the polarizer is laminated, it is preferable that the outermost surface of the functional layer satisfies the above-mentioned surface roughness SRa and SRz. Having the above-mentioned surface roughness prevents scratches on the film and functional layer surface of the light source unit while maintaining good sliding properties with the various film surfaces of the light source unit of the liquid crystal display device, and prevents deterioration of image quality due to long-term use.

[0211] When a functional layer other than the anti-glare layer is provided on the high-Re polarizer protective film, it is preferable that the upper limits of SRa and SRz on the outermost surface of the functional layer are the same as the upper limits of SRa and SRz of the polarizer protective film described above. It is also preferable that the lower limits of SRa and SRz on the outermost surface of the functional layer are the same as the lower limits of SRa and SRz of the polarizer protective film described above.

[0212] (Polarizer) As polarizers, for example, those made by adsorbing iodine or an organic dichroic dye onto uniaxially stretched polyvinyl alcohol (PVA), those made by oriented a liquid crystal compound and an organic dichroic dye, or liquid crystalline polarizers made of liquid crystalline dichroic dyes, wire grid type polarizers, etc., can be used without particular limitation.

[0213] A polarizer in the form of a film, in which iodine or an organic dichroic dye is adsorbed onto uniaxially stretched polyvinyl alcohol (PVA), and a polarizer protective film wound into a roll can be bonded together using a PVA-based adhesive or adhesive, such as an ultraviolet-curing type, and then wound into a roll. The thickness of this type of polarizer is preferably 5 to 30 μm, more preferably 8 to 25 μm, and particularly preferably 10 to 20 μm. The thickness of the adhesive or adhesive is preferably 1 to 10 μm, more preferably 2 to 5 μm.

[0214] Furthermore, polarizers are also preferably made by coating an unstretched substrate such as PET or polypropylene with PVA, uniaxially stretching it together with the substrate, and adsorbing iodine or an organic dichroic dye. When using this type of polarizer, the polarizer surface (the side not laminated with the substrate) of the polarizer laminated on the substrate and the polarizer protective film are bonded together with an adhesive or adhesive, and then the substrate used to manufacture the polarizer is peeled off, thereby bonding the polarizer protective film and the polarizer. In this case as well, it is preferable to bond them in a roll and then wind them up. The thickness of this type of polarizer is preferably 1 to 10 μm, more preferably 2 to 8 μm, and particularly preferably 3 to 6 μm. The thickness of the adhesive or adhesive is preferably 1 to 10 μm, and more preferably 2 to 5 μm.

[0215] In the case of liquid crystalline polarizers, a polarizer plate can be made by laminating a polarizer protective film with polarizers oriented using a liquid crystal compound and an organic dichroic dye, or by coating the polarizer protective film with a coating liquid containing a liquid crystalline dichroic dye, drying it, and then laminating the polarizers by light or heat curing. Methods for oriented the liquid crystalline polarizers include rubbing the surface of the object to be coated, and curing while irradiating with polarized ultraviolet light to align the liquid crystalline polarizers. The surface of the polarizer protective film may be directly rubbed and then coated with the coating liquid, or the coating liquid may be directly applied to the polarizer protective film and then irradiated with polarized ultraviolet light. It is also preferable to provide an orientation layer on the polarizer protective film before providing the liquid crystalline polarizers (i.e., laminating the liquid crystalline polarizers to the polarizer protective film via an orientation layer). Methods for providing the orientation layer include: A method of coating with polyvinyl alcohol and its derivatives, polyimide and its derivatives, acrylic resin, polysiloxane derivatives, etc., and then rubbing the surface to form an oriented layer (rubbing-oriented layer). A method of applying a coating solution containing a polymer or monomer having photoreactive groups such as cinnamoyl groups and chalcone groups, and a solvent, and irradiating it with polarized ultraviolet light to align and cure it to form an oriented layer (photo-oriented layer). These are some examples.

[0216] Alternatively, a polarizer can be bonded to a polarizer film by attaching a liquid crystalline polarizer to a release-type film in accordance with the above method, bonding the liquid crystalline polarizer surface and the polarizer film with an adhesive or bonding agent, and then peeling off the release-type film.

[0217] The thickness of the liquid crystalline polarizer is preferably 0.1 to 7 μm, more preferably 0.3 to 5 μm, and particularly preferably 0.5 to 3 μm. The thickness of the adhesive or tack is preferably 1 to 10 μm, more preferably 2 to 5 μm.

[0218] (Lamination of polarizer and polarizer protective film) The high-Re polarizer protective film is preferably laminated on the side opposite to the polarizer cell. When the polarizer and the high-Re polarizer protective film are laminated to form a polarizer plate, the angle between the absorption axis of the polarizer and the slow axis of the high-Re polarizer protective film is preferably 90 degrees ± 7 degrees or less. Here, "or less" applies only to the number after ±, meaning 83 to 97 degrees, and the same applies to the following. This angle means that the angle on the acute side is 83 degrees or more and 90 degrees or less. The angle between the absorption axis of the polarizer and the slow axis of the high-Re polarizer protective film is more preferably 90 degrees ± 5 degrees or less, even more preferably 90 degrees ± 3 degrees or less, particularly preferably 90 degrees ± 2 degrees or less, and most preferably 90 degrees ± 1.5 degrees or less. It is preferable that the above angle is maintained over the entire range of the polarizer plate. It is also preferable that the angle between the absorption axis of the polarizer and the slow axis of the high-Re polarizer protective film is 0 degrees ± 7 degrees or less. Here, "below" applies only to the number immediately following the ± sign, meaning -7 to 7 degrees, and the same applies to the following. The angle in question means that the acute angle is between 0 and 7 degrees. The angle between the absorption axis of the polarizer and the slow axis of the high-Re polarizer protective film is more preferably 0 degrees ± 5 degrees or less, even more preferably 0 degrees ± 3 degrees or less, particularly preferably 0 degrees ± 2 degrees or less, and most preferably 0 degrees ± 1.5 degrees or less. It is preferable that the above angles apply to the entire range of the polarizer plate.

[0219] In terms of industrial production, it is preferable that the angle between the absorption axis of the polarizer and the slow phase axis of the high-Re polarizer protective film is approximately perpendicular (90 degrees ± 7 degrees or less). Furthermore, when the angle between the absorption axis of the polarizer and the slow phase axis of the high-Re polarizer protective film is approximately perpendicular, the direction of vibration of the polarization transmitted through the polarizer is in the direction of the slow phase axis (high refractive index) of the polarizer protective film, and the application of the present invention is effective in that reflection at the interface of the polarizer protective film is likely to occur.

[0220] As described above, the present invention includes a technique to adjust the retardation of the film when observed from a specific direction, so that the color unevenness is less visible, when a birefringent resin film is used as a polarizer protective film and a KSF light source is used. By keeping the angle difference between the absorption axis of the polarizer and the slow axis of the polarizer protective film within a certain range, it is possible to accurately match the direction in which color unevenness is likely to occur with the retardation range in which the color unevenness of the film is less visible, thereby enabling more advanced control over the occurrence of color unevenness.

[0221] Furthermore, by setting the angle between the polarizer's absorption axis and the polarizer's protective film's slow axis within the above range, it is possible to prevent the occurrence of color splotches when observing obliquely from the normal direction toward the polarizer's absorption axis or a direction perpendicular to the absorption axis. When the angle between the polarizer's absorption axis and the polarizer's protective film's slow axis is exactly 0 degrees or 90 degrees, even when observing obliquely toward the polarizer's absorption axis or a direction perpendicular to the absorption axis, the direction of polarization vibration will be 0 degrees or 90 degrees with the slow axis of the high-Re film, and linear polarization will not be disturbed. However, if the angle between the polarizer's absorption axis and the polarizer's protective film's slow axis deviates beyond the above range, linear polarization will be disturbed and become elliptical polarization, and color splotches may be observed.

[0222] Furthermore, when the polarizer protective film was a high-Re film with a wavelength exceeding 8000 nm, and a conventional yellow phosphor was used as the light source, color unevenness was observed due to the influence of external light such as fluorescent lamps when the angle between the absorption axis of the polarizer and the slow phase axis of the polarizer protective film deviated significantly from 0 or 90 degrees.

[0223] On the other hand, as described above, the color spots that are controlled in this invention by adjusting the angle between the absorption axis of the polarizer and the slow axis of the polarizer protective film are color spots that occur due to reasons related to the KSF light source itself. The color variations controlled by this invention are considered to require more advanced adjustment for the following reasons. Color variations caused by high-intensity backlighting are more noticeable than color variations caused by indoor lighting. • Liquid crystal display devices using KSF light sources tend to show color unevenness due to their excellent color reproduction. Liquid crystal display devices using KSF light sources are preferred for large-scale liquid crystal display devices. Such high-quality, large-scale liquid crystal display devices are often used for projections in home theaters and museums, and in these cases, color variations originating from the backlight source become more noticeable when the room lighting is dimmed. • Indoor lighting is increasingly shifting from fluorescent lamps to white LED lighting using yellow phosphors, making the iridescence originating from KSF light sources more noticeable. In the manufacture of polarizing plates, it is common practice to produce a long polarizing plate by laminating a polarizer onto a long polarizer protective film, and then cutting it to the required width and length for use in image display devices. Therefore, in order to keep the optical properties and variations of these properties of the polarizer protective film used in the polarizing plates of image display devices within the aforementioned range, it is preferable to use a long polarizing plate in which these optical properties in the TD direction of the polarizer protective film are within the required range and variation range as described above. To this end, when manufacturing a long polarizing plate, it is preferable to use a polarizer protective film in which these optical properties in the TD direction of the film are within the required range as described above. Furthermore, for the MD direction, it is preferable to use a film in which the range of thickness variation is within the aforementioned range over the entire length of the long polarizer protective film. At this time, since it is difficult to measure the thickness at 100 mm intervals over the entire length of the MD direction, it is also possible to use thickness measurement data from online measurement data or to adopt the thickness variation in the MD direction obtained based on data measured at wide intervals. The width of the long polarizing plate and the long polarizer protective film is preferably 400 to 3000 mm, more preferably 500 to 2500 mm, and even more preferably 600 to 2200 mm. The length of the long polarizing plate and the polarizer protective film is preferably 100 to 10000 m, more preferably 300 to 7000 m, and even more preferably 500 to 5000 m.

[0224] (The side of the polarizer facing the liquid crystal cell) The surface of the polarizer facing the liquid crystal cell may be directly bonded to the liquid crystal cell with an adhesive or bonding agent, or a hardened layer may be provided on the polarizer, or a polarizer protective film different from the high-Re polarizer protective film described above may be provided. A preferred cured layer is the aforementioned hard coat layer.

[0225] Examples of polarizer protective films on the liquid crystal cell side include cellulose-based (TAC) films, acrylic films, and polycyclic olefin (COP) films. The polarizer protective film on the liquid crystal cell side may have near-zero retardation, or it may be a phase difference film, also known as an optical compensation film, used to control color tone changes when the display screen is viewed from an oblique angle.

[0226] To achieve the required phase difference in an optical compensation film, methods include stretching the film, coating the film with a phase difference layer such as a liquid crystal compound, or separately providing a phase difference layer such as a liquid crystal compound on a release film and transferring it. The liquid crystal compound used to form the phase difference layer is selected according to the required phase difference characteristics, such as a rod-shaped liquid crystal compound or a discotic liquid crystal compound. It is preferable that the liquid crystal compound has photocurable reactive groups such as double bonds to fix its orientation state. To orient the liquid crystal compound and create a phase difference, an orientation layer is provided as a layer below the phase difference layer, and the orientation layer is rubbed or irradiated with polarized ultraviolet light to provide orientation control so that the liquid crystal compound coated on top of it is oriented in a specific direction.

[0227] The phase difference of the optical compensation film can be set appropriately depending on the type of liquid crystal cell used, the required viewing angle, and other factors.

[0228] The phase difference layer can be provided by coating it with a phase difference layer composition coating. The phase difference layer composition coating may contain a solvent, polymerization initiator, sensitizer, polymerization inhibitor, leveling agent, polymerizable non-liquid crystal compound, crosslinking agent, etc. These can be those described in the sections on the orientation control layer and the liquid crystal polarizer.

[0229] A phase difference layer is formed by coating a phase difference layer composition paint onto the release surface or orientation control layer of a release film, followed by drying, heating, and curing.

[0230] These conditions, as well as those described in the sections on the alignment control layer and liquid crystal polarizer, are preferred conditions.

[0231] When bonding a polarizer to a polarizer protective film or phase difference film, an adhesive or bonding agent is used. Water-based adhesives such as polyvinyl alcohol-based adhesives or photocurable adhesives are preferably used. Examples of photocurable adhesives include acrylic and epoxy adhesives. Acrylic adhesives are preferably used as bonding agents. The optical compensation film, phase difference film, and phase difference layer described above are collectively referred to as the optical compensation layer.

[0232] Furthermore, if the polarizer is a circular polarizer used for anti-reflection in electroluminescent display devices, a λ / 4 phase difference layer is provided on the image display cell surface of the polarizer. The λ / 4 phase difference layer can be provided in the same manner as the optical compensation layer described above. The λ / 4 phase difference layer may also be a composite λ / 4 phase difference layer, which is a combination of a λ / 4 phase difference layer and a λ / 2 phase difference layer.

[0233] Except when an anti-glare layer is present, the haze of the polarizing plate is preferably 5% or less, more preferably 3% or less, even more preferably 2% or less, and particularly preferably 1.5% or less. The lower limit of the haze is preferably 0.01% or more, and even more preferably 0.1% or more.

[0234] (Liquid crystal cell) A liquid crystal cell consists of a liquid crystal compound sealed between thin substrates, such as glass, on which circuits are formed. When the substrate is glass, the thickness is preferably 1 mm or less, more preferably 0.7 mm or less from the viewpoint of thinning, even more preferably 0.5 mm or less, and particularly preferably 0.4 mm or less.

[0235] While the liquid crystal cell type is not particularly limited, VA and IPS methods are preferred for applying the present invention because they exhibit minimal color shift when viewed from an oblique direction, and in these methods, the absorption axis of the polarizing plate is parallel to or perpendicular to the long side direction of the liquid crystal cell.

[0236] For the color filter incorporated into the liquid crystal cell, it is preferable that the maximum and minimum transmittances for the 420nm to 460nm wavelength range of the blue pixels are both 80% or higher, and more preferably 85% or higher. The difference between the maximum and minimum transmittances for the 420nm to 460nm wavelength range is preferably 4% or less, and more preferably 3% or less.

[0237] (LCD panel) Preferably, polarizing plates are bonded to the viewing side and the light source side of the liquid crystal cell, respectively, to form a liquid crystal display panel. The bonding is preferably done with an adhesive. An acrylic-based adhesive is preferably used.

[0238] In a liquid crystal panel, the polarizer using the above-mentioned high-Re polarizer protective film may be either the polarizer on the light source side or the polarizer on the viewing side, or both polarizers may be used.

[0239] In particular, when using a polarizer protective film on the light source side of a polarizer plate, for example, a film with an in-plane retardation in the range of 3000 to 30000 nm, color unevenness is likely to occur when combined with a KSF light source for reasons such as the light passing through the polarizer protective film being affected by the polarizer, and the light incident on the high-Re polarizer protective film being linearly polarized because it has passed through a reflective polarizer plate. Therefore, it is preferable to use a polarizer plate with the high-Re polarizer protective film described above as the light source side polarizer plate.

[0240] When using a polarizer with the above-mentioned high-Re polarizer protective film only on the light source side polarizer, the viewing side polarizer may be a polarizer with a polarizer protective film of other properties on the side opposite to the cell. Examples of polarizer protective films of other properties include birefringent resin films with an in-plane retardation of 1500 to 30000 nm, TAC films, acrylic films, COP films, and other zero retardation films. The birefringent resin film is preferably the resin exemplified in the high-Re polarizer protective film example. Alternatively, a resin film using a birefringent resin such as PET with an in-plane retardation of preferably 200 nm or less, and more preferably 150 nm or less, may also be used. Even with a polarizer protective film of other properties, it is preferable that the above-mentioned functional layer is provided on the polarizer protective film. In particular, when using a birefringent resin film with an in-plane retardation of 1500 to 30000 nm, providing an anti-reflective layer or a low-reflective layer can reduce color unevenness originating from the polarizer protective film on the viewing side polarizer. In this case, the polarizer of the viewing-side polarizer, the surface of the polarizer facing the liquid crystal cell, and adhesives and bonding agents are the same as those described for polarizers using a high-Re polarizer protective film.

[0241] When using a birefringent resin film with an in-plane retardation of 1500 to 30000 nm, the angle between the slow axis of the birefringent resin film and the absorption axis of the polarizer is preferably approximately 0 degrees (0 degrees ± 7 degrees) or approximately 90 degrees (90 degrees ± 7 degrees). If the angle is approximately 90 degrees, the in-plane retardation is preferably 3000 nm or more, more preferably 4500 nm or more, even more preferably 6000 nm or more, and particularly preferably 7000 nm or more. The upper limit of the in-plane retardation is preferably 12000 nm. Such a film can be produced, for example, by stretching polyester such as PET 3 to 6 times in the TD direction using a tenter or the like. When the angle is approximately 0 degrees, the in-plane retardation is preferably 9000 nm or less, more preferably 8000 nm or less, even more preferably 7000 nm or less, and particularly preferably 6000 nm or less. Such a film can be produced, for example, by stretching a polyester such as PET 3 to 6 times in the MD direction between rolls at different peripheral speeds. The Re / Rth of the above birefringent resin film is preferably 0.6 to 1.2, and more preferably 0.7 to 1.

[0242] When using a polarizer with the above-mentioned high-Re polarizer protective film only on the viewing-side polarizer, it is preferable that the polarizer protective film on the side of the light source-side polarizer opposite to the cell be a zero-retardation film such as a TAC film, acrylic film, or COP film. Furthermore, it is preferable that the zero-retardation film has an in-plane retardation of 50 nm or less.

[0243] Generally, to ensure that images can be recognized even when wearing polarized sunglasses, the polarizer on the viewing side has a vertical transmission axis, and as a result, the polarizer on the light source side has a horizontal transmission axis. In polarizers using a stretched PVA polarizer and a polyester high-Re polarizer protective film, the transmission axis of the polarizer is approximately parallel to the slow phase axis of the polarizer protective film, so the slow phase axis is vertical on the viewing side polarizer and horizontal on the light source side polarizer. Furthermore, since image display devices are rectangular and are often installed with their longer sides horizontal, the image is viewed from a more oblique angle when viewed along the longer side, and it is preferable that color unevenness from this direction be further reduced. Therefore, in a rectangular liquid crystal display device installed with its long side horizontal, it is preferable to set the high Re polarizer protective film of the light source side polarizer to a higher range among the above preferred ranges for FI(45), FI(30), and FI(60).

[0244] When polarizers using the above-mentioned high-Re polarizer protective film are used for both the light source-side polarizer and the viewing-side polarizer, the characteristics of the high-Re polarizer protective film on each polarizer may be the same or different, as long as they are within the specified range. If they are different, it is preferable to make the FI(45), FI(30), and FI(60) of the high-Re polarizer protective film on the light source-side polarizer higher than those on the viewing-side. Furthermore, the polarizer of the viewing-side polarizer, the liquid crystal cell-side surface of the polarizer, and the adhesive or bonding agent may be the same or different.

[0245] The liquid crystal display device of the present invention may incorporate a touch panel function. Methods for providing a touch panel function to a liquid crystal display device include providing a separate touch sensor on the viewing side of the liquid crystal cell, using an in-cell or on-cell type where electrodes as touch sensors are provided on the substrate of the liquid crystal cell, and providing electrodes as touch sensors on the surface cover sheet. [Examples]

[0246] The present invention will be described more specifically below with reference to examples, but the present invention is not limited by the following examples, and can be implemented with appropriate modifications within the scope that is consistent with the spirit of the present invention, and all such modifications are included within the technical scope of the present invention. The evaluation methods for physical properties, etc., in the following examples are as follows.

[0247] (1) Spectrum of the light source The liquid crystal panel was removed from the liquid crystal display device, and the central part of the light source unit, including the diffuser plate and brightness enhancement film, was measured at a polar angle of 0 degrees, approximately 5 mm away from the light source unit, using a Hamamatsu Photonics PMA-12 (C10027-01) multi-channel spectrophotometer. An ND-8 filter was used to adjust the light intensity during the measurement. The measurement pitch was approximately 0.75 nm.

[0248] (2A) Retardation from an oblique direction The OPTIPRO-STD manufactured by Syntec Co., Ltd. was used as the measuring device. Multiple samples were cut continuously in the direction of the phase-advancing axis, with 40 mm in the phase-advancing axis direction and 60 mm in the phase-slowing axis direction from the center of the film, and placed on the sample stage so that the phase-slowing axis direction was approximately parallel to the X direction of the measurement stage. The measurements were performed under the following conditions. · Axis definition Slow axis: 0deg ··Axis search:ON Output data: Retardation ·Wavelength: Monochromatic light 589nm Sample stage ·Incident angle: START-0deg / END-50deg / STEP-5deg Slow axis (direction of azimuth angle to be measured): START-30deg / END-60deg / STEP-5deg From the calculated measurements, the values ​​for each sample with a polar angle of 50 degrees and azimuth angles of 30, 45, and 60 degrees were selected, and the average of the measurements of the three samples was taken as Rob(30), Rob(45), and Rob(60) for that film. Since the measurements of each sample may contain errors due to ripple noise, it was checked whether the data changed smoothly with respect to the changes in polar and azimuth angles around the selected polar and azimuth angles. If the change was not smooth, the same sample was reattached and remeasured, or the sample was changed and measured again, and the average of the three normally measured samples was taken. When changing samples, a new sample for remeasurement was cut out adjacent to it in the direction of the phase-advancing axis. (2B) Retardation from an oblique direction The OPTIPRO-STD manufactured by Syntec Co., Ltd. was used as the measuring device. The sample was 40 mm in the leading phase axis direction and 60 mm in the slow phase axis direction, and was placed on the sample stage so that the slow phase axis direction was approximately parallel to the X direction of the measurement stage. The measurement was performed under the following conditions. · Axis definition Slow axis: 0deg ··Axis search:ON Output data: Retardation ·Wavelength: Monochromatic light 589nm Sample stage ·Incident angle: START-0deg / END-50deg / STEP-5deg Slow axis (direction of azimuth angle to be measured): START-30deg / END-60deg / STEP-5deg From the calculated measurements, the values ​​for each sample with a polar angle of 50 degrees and azimuth angles of 30, 45, and 60 degrees were selected, and the average of the measurements of the three samples was taken as Rob(30), Rob(45), and Rob(60) for that film. Since the measurements of each sample may contain errors due to ripple noise, it was checked whether the data showed a smooth change in polar angle and azimuth around the selected polar angle and azimuth angles. If the change was not smooth, the same sample was reattached and measured again, and the average of the three normally measured values ​​was taken.

[0249] For cutting samples from a long polarizer protective film, the first sample was cut from the center of the width of the long film, which had been slit to the width required for bonding with the polarizer. The second and third samples were then cut from both ends. Subsequently, samples were cut from the position where the first sample was cut toward both ends of the film width. At this time, the center of the 40 x 60 mm sample was spaced 100 mm apart, and the ends were cut to a position where samples of the specified size could be cut. Furthermore, if the width of the remaining end was 60 mm or more after cutting to both ends, a sample was cut from the center of the end width.

[0250] For polarizing plates cut into single sheets for incorporation into a display device, if the long or short side coincided with the width direction of the long polarizer protective film, the values ​​measured in the width direction of the long film sampled above were adopted as the long or short side values. Furthermore, for the long or short sides of the single sheet polarizing plate that coincided with the length direction of the long polarizer protective film, 11 samples were cut from the center of the long polarizer protective film at 100mm intervals in the length direction and measured; these values ​​were used as substitutes. In the examples, since the variation in the TD direction was greater than the variation in the MD direction for all films, the variation in the TD direction was adopted. When cutting a sample from a polarizing plate incorporated into a display device, for example, the polarizing plate can be immersed in warm water at about 50°C, the polarizer protective film can be gently peeled off from the edges, and the sample can be cut from the resulting polarizer protective film. In this case, the sample is cut from the center of the single-wafer film toward both ends in the long and short directions using the method described above.

[0251] (3) Film thickness and variation Measurements were taken using an electric micrometer (Millitron 1245D, manufactured by FineLewf Co., Ltd.). The film thickness was measured at 50 mm intervals from the center in the width direction toward both ends in the TD direction, and the variation in thickness in the TD direction was calculated as (maximum value - minimum value) / average value × 100 (%). In addition, the thickness was measured at 100 points in the MD direction at similar intervals from the center of the film in the width direction, and the variation in thickness in the MD direction was similarly calculated. The larger of the thickness variation in the TD direction and the thickness variation in the MD direction was taken as the film thickness variation. The film thickness was taken as the average value of the thickness in the TD direction.

[0252] (4) The crystalline axis of the polarizer A polarizing filter and polarizer with known absorption axes were superimposed and placed on a surface light source. The polarizing filter was rotated until it was darkest, and the direction of the polarizer's absorption axis was set to 90 degrees from the direction of the polarizing filter's absorption axis. In the case of a long polarizer made of PVA stretched in the longitudinal direction, the longitudinal direction is the absorption axis, so the longitudinal direction can be considered the absorption axis.

[0253] (5) The slow axis direction of the film The measurements were taken using a molecular orientation analyzer (MOA-6004 molecular orientation analyzer, manufactured by Oji Instruments Co., Ltd.).

[0254] (6) Three-dimensional surface roughness Using a stylus-type three-dimensional roughness meter (SE-3AK, manufactured by Kosaka Research Institute Co., Ltd.), measurements were taken along the longitudinal direction of the film at a cutoff value of 0.25 mm over a measurement length of 1 mm, under conditions of a needle radius of 2 μm and a load of 30 mg, with a needle feed speed of 0.1 mm / second. The measurement was divided into 500 points at 2 μm intervals, and the height of each point was input into a three-dimensional roughness analyzer (SPA-11). The same procedure was performed continuously 150 times along the width direction of the film at 2 μm intervals, i.e., over a width of 0.3 mm, and the data was input into the analyzer. Next, the average surface roughness (SRa) and the average surface roughness (SRz) at 10 points were determined using the analyzer. Three measurements were performed, and the average value was adopted.

[0255] (7) Hayes In accordance with JIS-K7105, the haze of the film was measured using a turbidimeter (NHD2000, manufactured by Nippon Denshoku Industries).

[0256] (8) Light transmittance at a wavelength of 380 nm Using a spectrophotometer (Hitachi, Ltd., U-3500 model), the light transmittance in the wavelength range of 300-500 nm was measured with an air layer as the standard, and the light transmittance at a wavelength of 380 nm was determined.

[0257] (9) Intrinsic viscosity 0.2 g of the sample was dissolved in 50 ml of a mixed solvent of phenol / 1,1,2,2-tetrachloroethane (60 / 40 (weight ratio)) and measured using an Ostwald viscometer at 30°C.

[0258] (10A) Evaluation of color spots in oblique directions The backlight unit and LCD panel were removed from a commercially available television (Toshiba REGZA43J10X), and the polarizing plate was peeled off the LCD panel. The fabricated polarizing plate was then placed on the surface of the LCD panel from which the polarizing plate had been peeled off, with polarizer protective films A-K positioned on the opposite side of the LCD cell from the polarizer, and the absorption axis direction of the polarizer being the same as that of the original polarizing plate. The backlight unit was then attached to create an evaluation display. The space between the LCD cell and the polarizing plate was filled with deionized water to minimize reflection. The evaluation display was placed horizontally on a desk and displayed entirely in white. The entire screen was viewed from a distance of approximately 2 meters, at azimuth angles of approximately 45 degrees and 135 degrees (midway between the long and short sides of the screen), and at a polar angle (angle with the normal direction) of 50 degrees, to observe the state of color unevenness. Five people evaluated the display using the following three-level ranking system, and the average value was rounded to obtain the evaluation score. The angle is measured relative to the center of the screen. The evaluation was conducted in a darkened room with the backlight intensity set to maximum. 1 point: There were areas where unacceptable color variations were observed. 3 points: Color variations were present but acceptable. 5 points: The color variations were not a concern. As described below, the evaluation was performed with only the polarizing filter on the viewing side replaced, only the polarizing filter on the light source side replaced, and both polarizing filters replaced. (10B) Evaluation of color spots in oblique directions The backlight unit and LCD panel were removed from a commercially available television (Toshiba REGZA43J10X), and the polarizing plate from the LCD panel was peeled off. A newly fabricated polarizing plate was placed on the surface of the LCD panel from which the polarizing plate had been peeled off, so that the high-Re polarizer protective film was on the opposite side of the LCD cell from the polarizer, and the absorption axis direction of the polarizer was the same as that of the original polarizing plate. The backlight unit was then attached to create an evaluation display. The space between the LCD cell and the polarizing plate was filled with deionized water to minimize reflection. The evaluation display was placed horizontally on a desk and displayed entirely in white. At a polar angle (angle with the normal direction) of 50 degrees, the evaluation participants walked around the desk where the display was placed, approximately 2 meters away, and observed the entire screen to check for striped color patches and color uniformity. Five people evaluated the display using the following three-level ranking system, and the average value was rounded to obtain the evaluation score. The angle was measured relative to the center of the screen. The evaluation was conducted in a darkened room with the backlight intensity set to maximum. One point: Striped color patches and uneven color tones were observed in the peripheral areas of the screen, particularly at the far edges. 3 points: Some unevenness in color tone was observed in the distant edges of the screen, but it was acceptable. 5 points: The unevenness of the color tone was not a concern. The emission spectrum of the light source is shown in Figure 1, and as mentioned above, the peak-to-peak distance (Wd) was 20.6 nm and the median wavelength (Wc) was 622.1 nm.

[0259] (11) Horizontal and vertical color spot evaluation Similar to the diagonal color spot evaluation, an evaluation display was prepared and set to display a completely white image. The entire screen was viewed from the front at an angle along the longer side of the screen, and the state of color spotting was observed. The evaluation was conducted by five people, and the following three ranks were assigned by consensus. The angle is the angle from the center of the screen. The evaluation was conducted in a dark room with the backlight intensity set to maximum. Rank 1: Iridescence was observed at an angle of approximately 60 degrees from the front. Rank 3: Color variations were observed at an angle of approximately 70 degrees from the front. Rank 5: The iridescence was not observed until viewed from directly to the side.

[0260] (12) Inspection of foreign matter in the film Place a test polarizer on the side of the fabricated polarizer with the high-Re polarizer protective film so that it is in a cross-Nicol state with the fabricated polarizer. The test polarizer should be made of TAC film with no phase difference on both sides and free of scratches and foreign matter. In this state, perform the inspection using a Nikon universal projector V-12 (projection lens 50x, transmitted illumination light beam switching knob 50x, transmitted light inspection). If foreign matter is present in the high-Re polarizer protective film, light will be transmitted through that area, making it appear to shine brightly. Count the number of areas with a major axis of 100 μm or more, areas between 50 μm and 100 μm, and areas between 20 μm and 50 μm, and calculate the total number of each across the entire polarizer. If the major axis could not be distinguished, the defective portion caused by the foreign matter detected by the method described above was cut from the polarizing plate, and the major axis was determined by observing it at increased magnification using a polarizing microscope. At this time, the high-Re polarizer protective film side of the polarizing plate was facing upwards, and the polarization direction was made parallel to the polarization direction of the polarizer on the light source side of the polarizing microscope.

[0261] (13) Micro-image uniformity The image was set to a white background, and the entire image was visually inspected from a distance of approximately 20 cm, checking for any abnormalities such as foreign objects, dark spots, areas with different color tones, or irregularities in pixel arrangement. The evaluation was conducted by five people, and the following three ranks were assigned by consensus. Rank 1: There are many abnormalities and the overall quality is poor. Rank 3: There were a few areas that felt abnormal, but the overall quality was not poor. Rank 5: No abnormalities were observed.

[0262] (14) Amount of antimony atoms in the residue After removing the easily adhesive layer from the film surface with a razor, the film was cut into small pieces with scissors. 0.1 g of each piece was dissolved in 20 mL of a parachlorophenol / tetrachloroethane mixed solvent (60 / 40 by weight ratio). This solution was then filtered using a hydrophilic PTFE membrane filter (H010A047A, Advantec Corporation) with an average pore size of 0.1 μm by water jet suction filtration. After filtration, the filter was recovered, and the residue on the filter was dissolved in nitric acid and brought to a fixed volume to prepare the test solution. Sample preparation was performed with N=3 for each sample. Sb in the test solution was measured using a high-resolution inductively coupled plasma mass spectrometer (HR-ICP-MS, Thermo Fisher Scientific K.K.).

[0263] (15) Image clarity and brightness Images of landscapes, people, and plants were displayed and observed from the surface, and their sharpness (contrast) and brightness were evaluated compared to the original image display device. The evaluation was conducted by five people, and they decided by consensus to assign the following three ranks. Rank 1: Clarity and brightness were reduced. Rank 3: Slightly less sharp and bright, but not to a noticeable degree. Rank 5: No difference was noticeable in clarity or brightness.

[0264] (16) Interference Color Evaluation (Formation of the hard coat layer) A hard coat layer forming solution with the following composition was applied to one side of the prepared substrate film using a #10 wire bar, dried at 70°C for 1 minute, and the solvent was removed. Then, the film with the hard coat layer was subjected to a high-pressure mercury lamp at 300 mJ / cm². 2 By irradiating with ultraviolet light, a surface protective film having a hard coat layer with a thickness of 5 μm was obtained. • Coating solution for forming a hard coat layer Methyl ethyl ketone 65.00% by mass Dipentaerythritol hexaacrylate 27.20% by mass (Shin Nakamura Chemical A-DPH) Polyethylene diacrylate 6.80% by mass (Shin Nakamura Chemical A-400) Photopolymerization initiator 1.00% by mass (Irgacure 184, manufactured by Ciba Specialty Chemicals) A hard-coated surface protection film was cut to an area of ​​10 cm (film width direction) x 15 cm (film length direction) to prepare a sample film. A black glossy tape (Nitto Denko Corporation, vinyl tape No. 21; black) was attached to the side of the obtained sample film opposite to the hard-coated layer. With the hard-coated layer side of this sample film facing upwards, it was observed using a three-wavelength daylight white light source (National Palook, FL 15EX-N 15W) at an oblique angle from above, at a position where the reflection was strongest when viewed visually.

[0265] The results of visual observations were ranked according to the following criteria. The observations were conducted by three individuals familiar with the evaluation process, and any disagreements were resolved through consensus. ○ and △ were considered passing grades. ○: Almost no interference colors are visible when observed from any angle. △: Slight iridescent coloration is observed. ×: Clear iridescent coloration is observed.

[0266] • Polyester A (PET(A)): Polyethylene terephthalate with an intrinsic viscosity of 0.62 dl / g PET(A) was manufactured using the following method. 86.4 parts by mass of terephthalic acid and 64.6 parts by mass of ethylene glycol were charged into an esterification reaction vessel, stirred, and heated until it reached 200°C. While stirring, 0.017 parts by mass of antimony trioxide as an ethylene glycol solution, 0.064 parts by mass of magnesium acetate tetrahydrate, and 0.16 parts by mass of triethylamine were added. Next, the mixture was heated under pressure and the esterification reaction was carried out at a gauge pressure of 0.34 MPa and 240°C. After that, the esterification reaction vessel was returned to atmospheric pressure and 0.014 parts by mass of phosphoric acid was added. Furthermore, the temperature was raised to 260°C over 15 minutes and 0.012 parts by mass of trimethyl phosphate was added. After 15 minutes, the mixture was dispersed using a high-pressure disperser, and after 15 minutes, the obtained esterification reaction product was transferred to a polycondensation reaction vessel and the polycondensation reaction was carried out under reduced pressure while heating. The polycondensation temperature reached was 280°C, and the reaction was carried out at this temperature for 20 minutes. After the polycondensation reaction was complete, the mixture was filtered through a Naslon filter with a 95% cut diameter of 5 μm, extruded in strand form from a nozzle, cooled and solidified using cooling water that had been pre-filtered (pore size: 1 μm or less), and then cut into pellets.

[0267] Polyester B (PET(B)): A molten mixture of 10 parts by mass of the ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one) and 90 parts by mass of PET(A). Furthermore, PET(B) was manufactured using the following method. Ten parts by mass of the dried ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one) and 90 parts by mass of the above PET(A) were mixed, and the mixture was filtered and pelletized using a kneading extruder in the same manner as above to obtain polyester B containing the ultraviolet absorber.

[0268] • Polyester C (PEN): Polyethylene naphthalate with an intrinsic viscosity of 0.58 dl / g

[0269] • Polyester D (PET(D)) The procedure was carried out in the same manner as PET(A), except that 0.04 parts by mass of antimony trioxide was used, only phosphoric acid was used as the phosphorus compound and added simultaneously with the other catalysts, and the maximum temperature of the polycondensation reaction was 290°C for 35 minutes. • Polyester E (PET(E)) The procedure was the same as for PET(A), except that PET(D) was used. Furthermore, these polyesters were filtered using a Naslon filter (nominal filtration accuracy: cuts 95% of 5μm particles) installed in the melting line used to extrude them into strands.

[0270] (Preparation of Adhesion Modification Coating Solution 1) A water-dispersible sulfonic acid metal base-containing copolymer polyester resin was prepared by conventional transesterification and polycondensation reactions to obtain a water-dispersible sulfonic acid metal base-containing copolymer polyester resin with the following composition: dicarboxylic acid components (relative to the total dicarboxylic acid components) consisting of 46 mol% terephthalic acid, 46 mol% isophthalic acid, and 8 mol% sodium 5-sulfonaisophthalate; and glycol components (relative to the total glycol components) consisting of 50 mol% ethylene glycol and 50 mol% neopentyl glycol. Next, 51.4 parts by mass of water, 38 parts by mass of isopropyl alcohol, 5 parts by mass of n-butyl cellsolve, and 0.06 parts by mass of a nonionic surfactant were mixed, and the mixture was heated and stirred until it reached 77°C. Then, 5 parts by mass of the above water-dispersible sulfonic acid metal base-containing copolymer polyester resin was added, and stirring continued until there were no more clumps of resin. After that, the resin aqueous dispersion was cooled to room temperature to obtain a uniform water-dispersible copolymer polyester resin liquid with a solid content concentration of 5.0% by mass. Furthermore, 3 parts by mass of aggregated silica particles (Silysia 310, manufactured by Fuji Silysia Co., Ltd.) were dispersed in 50 parts by mass of water. Then, 0.54 parts by mass of the aqueous dispersion of Silysia 310 was added to 99.46 parts by mass of the above water-dispersible copolymer polyester resin liquid, and 20 parts by mass of water was added while stirring to obtain adhesive modification coating solution 1. The coating solution was filtered through a cartridge filter with a particle size of 10 μm and 95% separation.

[0271] (Preparation of Adhesion Modification Coating Solution 2) (Polymerization of copolymerized polyester resins) In a stainless steel autoclave equipped with a stirrer, thermometer, and partial reflux condenser, 381 parts by mass of dimethyl naphthalate, 58.3 parts by mass of dimethyl terephthalate, 41.5 parts by mass of dimethyl-5-sodium sulfoisophthalate, 46.7 parts by mass of diethylene glycol, 245.8 parts by mass of ethylene glycol, and 0.5 parts by mass of tetra-n-butyl titanate were charged, and a transesterification reaction was carried out from 160°C to 220°C for 4 hours. The temperature was then raised to 255°C, the reaction system was gradually reduced in pressure, and the reaction was carried out under reduced pressure of 30 Pa for 1 hour and 30 minutes to obtain copolymer polyester resin (A-1). The obtained copolymer polyester resin was pale yellow and transparent. The composition measured by 1H-NMR was 2,6-naphthalenedicarboxylic acid / terephthalic acid / 5-sodium sulfoisophthalic acid / / ethylene glycol / diethylene glycol = 78 / 15 / 7 / / 90 / 10 (mol%).

[0272] (Preparation of aqueous dispersion of polyester) In a reactor equipped with a stirrer, thermometer, and reflux device, 20 parts by mass of polyester resin (A-1) and 15 parts by mass of ethylene glycol t-butyl ether were added and heated at 110°C, and the resin was dissolved by stirring. After the resin was completely dissolved, 65 parts by mass of water were gradually added to the polyester solution while stirring. After the addition, the liquid was cooled to room temperature while stirring to prepare an aqueous dispersion of milky white polyester (B-1) with a solid content of 20% by mass.

[0273] (Polymerization of blocked polyisocyanate crosslinking agents) A four-necked flask equipped with a stirrer, thermometer, reflux condenser, nitrogen inlet tube, and dropping funnel was placed under a nitrogen atmosphere. 600 parts of HMDI and 30 parts of a trihydric alcohol, polycaprolactone-based polyester polyol (Daicel Chemicals, Praxel 303, molecular weight 300), were charged, and the reactor temperature was maintained at 90°C for 1 hour under stirring to carry out the urethane reaction. After that, the reactor temperature was maintained at 60°C, and the isocyanuration catalyst tetramethylammonium capriate was added. When the yield reached 48%, phosphoric acid was added to stop the reaction and obtain polyisocyanate composition (C-1).

[0274] Next, a four-necked flask equipped with a stirrer, thermometer, reflux condenser, nitrogen blowing tube, and dropping funnel was placed under a nitrogen atmosphere. 100 parts of polyisocyanate composition (C-1), 19 parts of methoxypolyethylene glycol with a molecular weight of 400 (manufactured by Nippon Oil & Fats Co., Ltd., Uniox M400) (which reacts with 10% of the total isocyanate groups of the polyisocyanate), and 37 parts of propylene glycol monomethyl ether acetate were charged into the flask, and the mixture was maintained at 80°C for 7 hours. After that, the reaction solution temperature was maintained at 50°C, and 38 parts of methyl ethyl ketoxime were added dropwise. The infrared spectrum of the reaction solution was measured, and the isocyanate groups disappeared, yielding an aqueous block polyisocyanate resin (C-2) with a solid content of 80% by mass.

[0275] Preparation of Adhesion Modification Coating Solution 2 The following coating agents were mixed and filtered through a cartridge filter with a 95% separation rate and a particle size of 10 μm to prepare coating solution 2. Particle A is SnO2 with a refractive index of 2.1, and particle B is silica particles with an average primary particle size of approximately 500 nm. Water 43.26% by mass Isopropanol 30.00% by mass Polyester aqueous dispersion (B-1) 20.07% by mass Aqueous block polyisocyanate resin (C-2) 0.74% by mass Particle A 5.58% by mass (Taki Chemical Co., Ltd. Ceramace S-8, solid content concentration 8% by mass) Particle B 0.30% by mass (Nippon Shokubai Seahostar KEW50, solid content concentration 15% by mass) Surfactant 0.05% by mass (Nisshin Chemical Industry Co., Ltd. Dynol 604, solid content concentration 100% by mass)

[0276] Preparation of Adhesion Modification Coating Solution 3 Adhesion-modifying coating solution 3 was obtained in the same manner as adhesion-modifying coating solution 2, except that the polyester aqueous dispersion was changed to B-2 and particle A was changed to SiO2 with a refractive index of 1.46 (Snowtex ZL manufactured by Nissan Chemical Industries, solid content concentration 40% by mass).

[0277] (Polarizer) A roll of polyvinyl alcohol film with a thickness of 80 μm, which was continuously stained in an iodine aqueous solution, was stretched five times in the transport direction, treated in a boric acid solution, washed with water, and dried to obtain a long polarizer.

[0278] (Polarizer protective film A) As raw materials for the intermediate layer of the base film, 90 parts by mass of particle-free PET(A) resin pellets and 10 parts by mass of PET(B) resin pellets containing an ultraviolet absorber were dried under reduced pressure (1 Torr) at 135°C for 6 hours, and then supplied to extruder 2 (for intermediate layer II). PET(A) was dried by a conventional method and supplied to extruder 1 (for outer layer I and outer layer III), respectively, and melted at 285°C. These two polymers were filtered using a stainless steel sintered filter medium (nominal filtration accuracy, 95% particle cut of 10 μm particles), laminated in a 2-layer 3-combination block, extruded into a sheet from a die, and then cooled and solidified using an electrostatic casting method on a casting drum with a surface temperature of 30°C to produce an unstretched film. At this time, the discharge rate of each extruder was adjusted so that the thickness ratio of layers I, II, and III was 10:80:10.

[0279] Next, a dry coating amount of 0.08 g / m² was applied to both sides of this unstretched PET film. 2 To achieve this, the above-mentioned adhesive modification coating solution 1 was applied and then dried at 80°C for 20 seconds. During the coating process, a cartridge filter with a particle size of 10 μm and 95% separation was installed in the line that supplied the coating solution 1 to the coating die to remove aggregated particles.

[0280] The unstretched film with this coating layer was guided to a tenter stretcher, and while holding the ends of the film with clips, it was guided to a 100°C tenter and stretched to 4.1 times its original width. Next, while maintaining the stretched width, it was treated for 10 seconds in a heat-setting zone at 190°C, and then a further 3.0% relaxation treatment was performed in the width direction to obtain a stretched PET film.

[0281] (Polarizer protective film B~H) A polarizer protective film as shown in Table 1 was obtained in the same manner as polarizer protective film A, except that the thickness of the unstretched film was adjusted.

[0282] (Polarizer protective film I)

[0283] An unstretched PET film, obtained in the same manner as polarizer protective film A except for adjusting the thickness, was heated to 110°C and stretched 1.08 times between rolls with different peripheral speeds. After drying, a coating amount of 0.08 g / m² was applied to both sides. 2 The above-mentioned adhesive modification coating solution was applied and dried in the same manner as described above. The resulting coated film was guided to a tenter stretcher, and while gripping the ends of the film with clips, it was guided to a 100°C tenter and stretched to 4.2 times its original width. Next, while maintaining the stretched width, it was treated in a heat-setting zone at 190°C for 10 seconds, and then a further 2.0% relaxation treatment was performed in the width direction to obtain a stretched PET film.

[0284] (Polarizer protective film J) A stretched PET film was obtained in the same manner as polarizer protective film I, except that the thickness was adjusted and the stretching between rolls was increased by 1.13 times.

[0285] (Polarizer protective film K) A stretched PET film was obtained in the same manner as polarizer protective film A, except that the thickness was adjusted, the tenter temperature was set to 105°C, and the stretching ratio was set to 5.3 times.

[0286] (Polarizer protective film L and M) An unstretched film was obtained in which the coating layer was formed in the same manner as polarizer protective film A, except for adjusting the thickness. The obtained unstretched film with the coating layer was guided to a tenter stretching machine, and while gripping the ends of the film with clips, it was guided to a tenter at 125°C and stretched to 4.0 times its original width. Next, while maintaining the stretched width, it was treated in a heat-setting zone at 225°C for 10 seconds, and then a further relaxation treatment of 2.0% in the width direction was performed to obtain a stretched PET film.

[0287] (Polarizer protective film N) As a raw material for the base film, particle-free PEN resin pellets were dried under reduced pressure at 135°C for 6 hours (1 Torr), then fed into an extruder and melted at 295°C. This polymer was filtered through a stainless steel sintered filter medium (nominal filtration accuracy of 95% removal of 10 μm particles), extruded in sheet form through a die, and then cooled and solidified using an electrostatic casting method on a casting drum with a surface temperature of 30°C to produce an unstretched film.

[0288] Next, the above-mentioned adhesive modification coating solution was applied to both sides of the unstretched PEN film so that the dry coating amount was 0.08 g / m2, and then dried at 80°C for 20 seconds.

[0289] The unstretched film with this coating layer was guided to a tenter stretcher, and while holding the ends of the film with clips, it was guided to a 130°C tenter and stretched to 4.0 times its original width. Next, while maintaining the stretched width, it was treated for 10 seconds in a heat-setting zone at 210°C, and then a further 3.0% relaxation treatment was performed in the width direction to obtain a stretched PEN film.

[0290] (Polarizer protective film O) A thickness-stretched PET film was obtained in the same manner as polarizer protective film A, except that the thickness was adjusted and the tenter temperature was set to 110°C and the stretching ratio to 5.4 times. The refractive index of film O was measured in the nx, ny, and nz directions using an Abbe refractometer, and the in-plane retardation was determined by multiplying the refractive index difference between nx and ny by the thickness, which was found to be 7198 nm.

[0291] (Polarizer protective film P) An unstretched PET film, obtained in the same manner as polarizer protective film A except for adjusting the thickness, was guided into a simultaneous biaxial stretcher at 125°C and stretched 6 times in the MD direction and 1.8 times in the TD direction. Next, it was treated in a heat-setting zone at 225°C for 10 seconds, and a relaxation treatment of 3% in the MD direction and 0.5% in the TD direction was performed to obtain a stretched PET film. The in-plane retardation of film P was 3880 nm.

[0292] The polarizer protective films obtained above were used by slitting the central portion where the orientation direction was nearly uniform (deviation from the TD direction or MD direction was 0.5 degrees or less). The characteristics of each polarizer protective film are shown in Table 1.

[0293] [Table 1]

[0294] (Fabrication of polarizing plates) (Fabrication of polarizing plates 1) Polarizer plates PA1 to PP1 were fabricated by laminating the polarizer protective film prepared above to one side of a polarizer and a triacetyl cellulose film (thickness 40 μm) to the opposite side using a roll-to-roll method. An ultraviolet-curing adhesive was used for lamination. In polarizer plates PA1 to PP1, the angle between the slow phase axis of the polarizer protective film and the absorption axis of the polarizer was 90 degrees, and in PP1 it was 0 degrees, with the misalignment being 0.5 degrees or less in all cases.

[0295] (Fabrication of polarizing plates 2) A triacetylcellulose roll film (40 μm thick) was laminated to one side of a polarizer using a roll-to-roll method, then cut into individual sheets. A polarizer protective film D, also cut into individual sheets, was laminated to the opposite side, with the lamination angle shifted as shown in Table 2, to obtain polarizer plates PD2 to PD4.

[0296] [Table 2]

[0297] (Evaluation using a polarizing plate on the light source side) The polarizer on the light source side was replaced with the polarizer prepared as described above, and the color patch evaluation was performed. The evaluation of color patch in the oblique direction was performed according to (10A). The results are shown in Table 3.

[0298] [Table 3]

[0299] In the case of polarizer PA1 using polarizer protective film A, Re was low and clear color splotches were observed from oblique directions. When the film thickness was increased from polarizer protective film B to H, and Re was increased, the color splotches from oblique directions, which were slightly observed with polarizer protective film B, initially decreased and then increased, and became clear when polarizer protective film H was used. As ΔFI / FI(45) increased with polarizer protective films I, J, L, and M, there was a tendency for color splotches from oblique directions to increase. Color splotches from horizontal and vertical directions were not observed in these samples. In the case of polarizer protective film K, where the resin is PEN, color unevenness was not noticeable as long as FI(45), etc., was within the appropriate range. Next, using polarizer protective film D, we evaluated the color patchiness in polarizers (PD2, PD3, PD4) when the angle between the slow axis and the polarizer's absorption axis was shifted from 90 degrees. As the shift increased, the color patchiness from oblique directions became partially stronger. In addition, color patchiness from horizontal and vertical directions also appeared as the shift increased.

[0300] (Evaluation using a polarizing plate on the viewing side) The polarizing plate on the viewing side was replaced with the polarizing plate prepared as described above, and the color patch evaluation was performed. The evaluation of the color patch in the oblique direction was performed according to (10A). The results are shown in Table 4. Note that, in order to observe the influence of the optical properties of the polarizer protective film, no anti-reflective layer or similar material was included.

[0301] [Table 4]

[0302] When used as a polarizer on the viewing side, the overall color unevenness was smaller than when used as a polarizer on the light source side, but the trend was the same.

[0303] (Evaluation using both the light source-side polarizer and the viewing-side polarizer) Both the light source-side polarizer and the viewing-side polarizer were replaced with the polarizers prepared as described above, and color unevenness was evaluated. The results are shown in Table 5. A reflection reduction layer, made by coating and drying Opstar TU-2360 (manufactured by Arakawa Chemical Industries, Ltd.) onto the polarizer protection film opposite the polarizer of each viewing-side polarizer, was provided. The reflectance measured from the reflection reduction layer side of polarizer protection film C, which was measured as a representative example, was 1.6%. The SRa on the reflection reduction layer surface was 2 nm, and the SRz was 75 nm. The reflectance was measured using a spectrophotometer (Shimadzu Corporation, UV-3150) at a wavelength of 550 nm, with the 5-degree reflectance being measured. For the measurement, black marker was applied to the side of the film opposite to the side with the anti-reflective (or low-reflectance) layer, and then black vinyl tape (Kyowa Vinyl Tape HF-737, 50 mm wide) was applied.

[0304] [Table 5]

[0305] As shown in Table 5, it was found that color unevenness is suppressed even when the present invention is used as a polarizer protective film for both the light source-side polarizer and the viewing-side polarizer. Furthermore, when the polarizer protective film used in the present invention is used as the polarizer protective film for the light source-side polarizer, color unevenness is suppressed even when a polyester film other than the polarizer protective film used in the present invention is used as the polarizer protective film for the viewing-side polarizer.

[0306] (Polarizer protective film a) As raw materials for the intermediate layer of the base film, 90 parts by mass of particle-free PET(A) resin pellets and 10 parts by mass of PET(B) resin pellets containing an ultraviolet absorber were dried under reduced pressure (1 Torr) at 135°C for 6 hours, and then supplied to extruder 2 (for intermediate layer II). PET(A) was dried by a conventional method and supplied to extruder 1 (for outer layer I and outer layer III), respectively, and melted at 285°C. These two polymers were filtered using a stainless steel sintered filter medium (nominal filtration accuracy, 95% particle cut of 10 μm particles), laminated in a 2-layer 3-combination block, extruded into a sheet from a die, and then cooled and solidified using an electrostatic casting method on a casting drum with a surface temperature of 30°C to produce an unstretched film. At this time, the discharge rate of each extruder was adjusted so that the thickness ratio of layers I, II, and III was 10:80:10.

[0307] Next, a dry coating amount of 0.08 g / m² was applied to both sides of this unstretched PET film. 2 To achieve this, the adhesive modification coating liquid 2 was applied and then dried at 80°C for 20 seconds. During the coating process, a cartridge filter with a particle size of 10 μm and 95% separation was installed in the line that supplied the coating liquid 2 to the coating die to remove aggregated particles.

[0308] The unstretched film with this coating layer was guided to a tenter stretcher, and while holding the ends of the film with clips, it was guided to a 100°C tenter and stretched to 4.1 times its original width. Next, while maintaining the stretched width, it was treated for 10 seconds in a 190°C heat-setting zone, and then a further 3.0% relaxation treatment was performed in the width direction to remove the uneven ends held by the clips, obtaining a stretched PET film with a width of 2000 mm and a length of 1000 m. The nozzle was adjusted so that the hot air from the tenter hit the film ends more during the preheating and the first half of the heat-setting process. The obtained film was divided in half in the width direction to obtain a stretched PET film a with a width of 1000 mm and a length of 1000 m. Furthermore, a special nozzle was used, with the flow distribution optimized through simulations using the resin to be used. The thickness measuring instrument in the film manufacturing line and the lip adjustment bolt of the nozzle were linked to control thickness variations in the TD direction, and product samples were taken once a stable state was achieved.

[0309] (Polarizer protective film b) The manufacturing process was carried out in the same manner as for film a, except that the amount of hot air hitting the film edge was changed by adjusting the nozzle in the first half of the preheating and heat setting processes, and the control program for the thickness measuring instrument and the lip adjustment bolt of the nozzle was improved.

[0310] (Polarizer protective film c) The manufacturing process was carried out in the same manner as for film a, except that nozzle adjustment was not performed in the first half of the preheating and heat setting processes, the preheating time was reduced to two-thirds, and coordinated control between the thickness measuring instrument and the lip adjustment bolt of the nozzle was not performed.

[0311] (Polarizer protective film d) A polarizer protective film d was obtained in the same manner as polarizer protective film a, except that a 1000 mm wide slit was made from the center.

[0312] (Polarizer protective film e) A polarizer protective film e was obtained in the same manner as polarizer protective film c, except that a 1000 mm wide slit was made from the center.

[0313] (Polarizer protective films f and g) Polarizer protective film f was obtained in the same manner as polarizer protective film a, except that the thickness was adjusted, the tenter temperature was set to 105°C, and the stretching ratio was set to 5.3 times. Polarizer protective film g was obtained in the same manner as polarizer protective film f, except that the thickness control program was the same as that of polarizer protective film b. The characteristics of each polarizer protective film are shown in Table 6.

[0314] [Table 6]

[0315] (Fabrication of polarizing plates) (Fabrication of polarizing plates 1) Polarizer plates Pa1 to Pg1 were fabricated by laminating the polarizer protective film prepared above to one side of a polarizer and a triacetyl cellulose film (thickness 40 μm) to the opposite side using a roll-to-roll method. An ultraviolet-curing adhesive was used for lamination. In each polarizer plate, the angle between the slow axis of the polarizer protective film and the absorption axis of the polarizer was 90 degrees, and the misalignment was 0.5 degrees or less.

[0316] [Table 7]

[0317] (Evaluation using both the light source-side polarizer and the viewing-side polarizer) Both the polarizing plate on the light source side and the polarizing plate on the viewing side were replaced with the polarizing plates prepared as described above, and oblique color spot evaluation was performed according to (10B). The results are shown in Table 8. Note that, in order to observe the influence of the optical properties of the polarizer protective film, no anti-reflective layer or similar material was included.

[0318] [Table 8]

[0319] (Polarizer protective film h) As raw materials for the intermediate layer of the base film, 90 parts by mass of particle-free PET(A) resin pellets and 10 parts by mass of PET(B) resin pellets containing an ultraviolet absorber were dried under reduced pressure (1 Torr) at 135°C for 6 hours, and then supplied to extruder 2 (for intermediate layer II). PET(A) was dried by a conventional method and supplied to extruder 1 (for outer layer I and outer layer III), respectively, and melted at 285°C. These two polymers were filtered using a stainless steel sintered filter medium (nominal filtration accuracy, 95% particle cut of 10 μm particles), laminated in a 2-layer 3-combination block, extruded into a sheet from a die, and then cooled and solidified using an electrostatic casting method on a casting drum with a surface temperature of 30°C to produce an unstretched film. At this time, the discharge rate of each extruder was adjusted so that the thickness ratio of layers I, II, and III was 10:80:10. The difference between the inner diameter of the gasket at the flange joint of the piping through which the molten resin passes and the inner diameter of the piping was 50 μm or less. At the start of operation, resin was discharged for 5 minutes three times at a flow rate 1.2 times the set resin extrusion rate, and then film production began. Film samples were taken starting 30 minutes after the start of production. The filter element was also replaced with a cleaned one at the start of operation.

[0320] Next, a dry coating amount of 0.08 g / m² was applied to both sides of this unstretched PET film. 2 To achieve this, the above-mentioned adhesive modification coating liquid 2 was applied and then dried at 80°C for 20 seconds. During the coating process, a cartridge filter with a particle size of 10 μm and 95% separation was installed in the line that supplied the coating liquid 2 to the coating die to remove particle aggregates.

[0321] The unstretched film with this coating layer was guided to a tenter stretcher, and while holding the ends of the film with clips, it was guided to a 100°C tenter and stretched to 4.1 times its original width. Next, while maintaining the stretched width, it was treated for 10 seconds in a heat-setting zone at 190°C, and then a further 3.0% relaxation treatment was performed in the width direction to obtain a stretched PET film.

[0322] (Polarizer protective film i) A polarizer protective film as shown in the table was obtained in the same manner as polarizer protective film h, except that the thickness of the unstretched film was adjusted.

[0323] (Polarizer protective film j) The film was sampled after being continuously manufactured for one week under the conditions of polarizer protective film h.

[0324] (Polarizer protective film k) The procedure was the same as for polarizer protective film h, except that the difference between the inner diameter of the gasket at the joint and the inner diameter of the piping was 200 μm, no resin discharge was performed, and the filter used was the same one used after one week of continuous production.

[0325] The polarizer protective films obtained above were used by slitting the central portion where the orientation direction was nearly uniform (deviation from the TD direction or MD direction was 0.5 degrees or less). The characteristics of each polarizer protective film are shown in Table 9.

[0326] [Table 9]

[0327] (Fabrication of polarizing plates) Polarizer plates Ph1 to Pk1 were fabricated by laminating the polarizer protective film prepared above to one side of the polarizer and a triacetyl cellulose film (thickness 40 μm) to the opposite side using a roll-to-roll method. An ultraviolet-curing adhesive was used for lamination. The angle between the slow axis of the polarizer protective film and the absorption axis of the polarizer was 90 degrees, and the misalignment was 0.5 degrees or less.

[0328] [Table 10]

[0329] (Evaluation of display devices) The polarizer on the light source side and the polarizer on the viewing side were replaced with the polarizers prepared as described above, and the evaluation was carried out. The evaluation of color spots in the oblique direction was performed according to (10A). The results are shown in Table 11. Note that, in order to observe the influence of the optical properties of the polarizer protective film, no anti-reflective layer or similar material was included.

[0330] [Table 11]

[0331] (Polarizer protective film l) As raw materials for the intermediate layer of the base film, 90 parts by mass of particle-free PET(A) resin pellets and 10 parts by mass of PET(B) resin pellets containing an ultraviolet absorber were dried under reduced pressure (1 Torr) at 135°C for 6 hours, and then supplied to extruder 2 (for intermediate layer II). PET(A) was dried by a conventional method and supplied to extruder 1 (for outer layer I and outer layer III), respectively, and melted at 285°C. These two polymers were filtered using a stainless steel sintered filter medium (nominal filtration accuracy, 95% particle cut of 10 μm particles), laminated in a 2-layer 3-combination block, extruded into a sheet from a die, and then cooled and solidified using an electrostatic casting method on a casting drum with a surface temperature of 30°C to produce an unstretched film. At this time, the discharge rate of each extruder was adjusted so that the thickness ratio of layers I, II, and III was 10:80:10. The difference between the inner diameter of the gasket at the joint of the pipe flange through which the molten resin passes and the inner diameter of the pipe was 50 μm or less. At the start of operation, resin was discharged for 5 minutes three times at a flow rate 1.2 times the set resin extrusion rate, and then film production began. Film samples were taken starting 30 minutes after the start of production. The filter element was also replaced with a cleaned one at the start of operation.

[0332] Next, a dry coating amount of 0.08 g / m² was applied to both sides of this unstretched PET film. 2 To achieve this, the above-mentioned adhesive modification coating liquid 2 was applied and then dried at 80°C for 20 seconds. During the coating process, a cartridge filter with a particle size of 10 μm and 95% separation was installed in the line that supplied the coating liquid 2 to the coating die to remove particle aggregates.

[0333] The unstretched film with this coating layer was guided to a tenter stretcher, and while holding the ends of the film with clips, it was guided to a 100°C tenter and stretched to 4.1 times its original width. Next, while maintaining the stretched width, it was treated for 10 seconds in a heat-setting zone at 190°C, and then a further 3.0% relaxation treatment was performed in the width direction to obtain a stretched PET film.

[0334] (Polarizer protective film m) A polarizer protective film as shown in Table 12 was obtained in the same manner as polarizer protective film l, except that the thickness of the unstretched film was adjusted.

[0335] (Polarizer protective film n)

[0336] The polarizer protective film l was constructed in the same manner as the original, except that PET(A) was replaced with a dry blend of PET(A) / PET(D) = 8 / 2, and PET(B) was replaced with a dry blend of PET(B) / PET(E) = 8 / 2.

[0337] (Polarizer protective film o) The polarizer protective film l was made the same as the original, except that PET(A) was changed to PET(D) and PET(B) was changed to PET(E).

[0338] The polarizer protective films obtained above were used by slitting the central portion where the orientation direction was nearly uniform (deviation from the TD direction or MD direction was 0.5 degrees or less). The characteristics of each polarizer protective film are shown in Table 12.

[0339] [Table 12]

[0340] (Fabrication of polarizing plates) A polarizer plate was fabricated by laminating the polarizer protective film prepared above to one side of a polarizer and a triacetyl cellulose film (40 μm thick) to the opposite side using a roll-to-roll method. An ultraviolet-curing adhesive was used for lamination. In each polarizer plate, the angle between the slow axis of the polarizer protective film and the absorption axis of the polarizer was 90 degrees, and the misalignment was 0.5 degrees or less in all cases.

[0341] [Table 13]

[0342] (Evaluation of display devices) The polarizer on the light source side and the polarizer on the viewing side were replaced with the polarizers prepared as described above, and the evaluation was carried out. The evaluation of color spots in the oblique direction was performed according to (10A). The results are shown in Table 14. Note that, in order to observe the influence of the optical properties of the polarizer protective film, no anti-reflective layer or similar material was included.

[0343] [Table 14]

[0344] (Polarizer protective film p) As raw materials for the intermediate layer of the base film, 90 parts by mass of particle-free PET(A) resin pellets and 10 parts by mass of PET(B) resin pellets containing an ultraviolet absorber were dried under reduced pressure (1 Torr) at 135°C for 6 hours, and then supplied to extruder 2 (for intermediate layer II). PET(A) was dried by a conventional method and supplied to extruder 1 (for outer layer I and outer layer III), respectively, and melted at 285°C. These two polymers were filtered using a stainless steel sintered filter medium (nominal filtration accuracy, 95% particle cut of 10 μm particles), laminated in a 2-layer 3-combination block, extruded into a sheet from a die, and then cooled and solidified using an electrostatic casting method on a casting drum with a surface temperature of 30°C to produce an unstretched film. At this time, the discharge rate of each extruder was adjusted so that the thickness ratio of layers I, II, and III was 10:80:10.

[0345] Next, a dry coating amount of 0.08 g / m² was applied to both sides of this unstretched PET film. 2 To achieve this, the above-mentioned adhesive modification coating solution was applied and then dried at 80°C for 20 seconds. During the coating process, a cartridge filter with a particle size of 10 μm and 95% separation was installed in the line that supplied the coating solution to the coating die to remove particle aggregates.

[0346] The unstretched film with this coating layer was guided to a tenter stretcher, and while holding the ends of the film with clips, it was guided to a 100°C tenter and stretched to 4.1 times its original width. Next, while maintaining the stretched width, it was treated for 10 seconds in a heat-setting zone at 190°C, and then a further 3.0% relaxation treatment was performed in the width direction to obtain a stretched PET film.

[0347] (Polarizer protective film q) A polarizer protective film as shown in Table 15 was obtained in the same manner as polarizer protective film p, except that the thickness of the unstretched film was adjusted.

[0348] (Polarizer protective film r)

[0349] A polarizer protective film as shown in Table 15 was obtained in the same manner as polarizer protective film p, except that adhesive modifier coating solution 3 was used.

[0350] The polarizer protective films obtained above were used by slitting the central portion where the orientation direction was nearly uniform (deviation from the TD direction or MD direction was 0.5 degrees or less). The characteristics of each polarizer protective film are shown in Table 15.

[0351] [Table 15]

[0352] (Fabrication of polarizing plates) A polarizer plate was fabricated by laminating the polarizer protective film prepared above to one side of a polarizer and a triacetyl cellulose film (40 μm thick) to the opposite side using a roll-to-roll method. An ultraviolet-curing adhesive was used for lamination. For each polarizer plate, the angle between the slow axis of the polarizer protective film and the absorption axis of the polarizer was 90 degrees, and the misalignment was 0.5 degrees or less in all cases.

[0353] [Table 16]

[0354] (Evaluation using a polarizing plate on the light source side) The evaluation was performed by replacing both the polarizer on the light source side and the polarizer on the viewing side with the polarizers prepared as described above. The evaluation of color spots in the oblique direction was performed according to (10A). The results are shown in Table 17. Note that, in order to observe the influence of the optical properties of the polarizer protective film, no anti-reflective layer or similar material was included.

[0355] [Table 17] [Industrial applicability]

[0356] The present invention makes it possible to provide an image display device that exhibits a wide color gamut and does not show noticeable color unevenness even when the image display device has an emission spectrum in which a steep peak appears in the red region. The present invention provides a liquid crystal display device that exhibits a wide color gamut and does not show noticeable color unevenness even when a light source with a steep emission spectrum in the red region, such as a KSF phosphor, is used as the backlight light source. The present invention provides a liquid crystal display device that exhibits minimal color unevenness, virtually no defects even when viewed up close, and has a wide color gamut, even when using a backlight source with a steep emission spectrum in the red region, such as a KSF phosphor. The present invention provides a liquid crystal display device that exhibits bright, vivid, and wide color gamut reproduction without noticeable color unevenness, even when using a backlight source with a steep emission spectrum in the red region, such as a KSF phosphor. The present invention makes it possible to provide an image display device that exhibits minimal color unevenness, a wide color gamut, and minimal interference colors, even in image display devices with a steep emission spectrum in the red region.

Claims

1. An image display device having an image display cell and at least one polarizing plate, the at least one polarizing plate is a polarizing plate in which light incident on the polarizing plate has a plurality of peak groups in a range of 600 to 650 nm, and the polarizing plate has a polarizer protective film having a 45-degree light source compatibility index (FI(45)) calculated by the following formula 1 of 0.4 to 0.62, The image display device, wherein the polarizer protective film having a 45-degree light source compatibility index (FI(45)) of 0.4 or more and 0.62 or less is a polyester film. FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1 Rob(45): Retardation when the polarizer protective film is measured in the in-plane direction of the film at an angle of 45 degrees from the slow axis direction to the fast axis direction and inclined by 50 degrees from the normal direction. Wd: Peak-to-peak distance (nm) Wc: central wavelength of the peak group (nm)

2. An image display device having an image display cell and at least one polarizing plate, the at least one polarizing plate is a polarizing plate in which light incident on the polarizing plate has a plurality of peak groups in a range of 600 to 650 nm; The at least one polarizing plate has a polarizer and at least one polarizer protection film, The at least one polarizer protective film has a 45-degree light source compatibility index (FI(45)) calculated by the following formula 1, the FI(45) being measured at 100 mm intervals along the long side direction and the FI(45) being measured at 100 mm intervals along the short side direction, both of which are 0.4 or more and 0.62 or less, The value obtained by subtracting the maximum value from the minimum value of the FI(45) measured at 100 mm intervals along the long side direction, and the value obtained by subtracting the maximum value from the minimum value of the FI(45) measured at 100 mm intervals along the short side direction are both 0.026 or less, The image display device, wherein the at least one polarizer protective film is a polyester film. FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1 Rob(45): Retardation when the polarizer protective film is measured in the in-plane direction of the film at an angle of 45 degrees from the slow axis direction to the fast axis direction and inclined by 50 degrees from the normal direction. Wd: Peak-to-peak distance (nm) Wc: central wavelength of the peak group (nm)

3. An image display device having an image display cell and at least one polarizing plate, the at least one polarizing plate has a polarizer protective film having a retardation (Rob(45)) of 7,500 nm or more and 11,700 nm or less when measured in an in-plane direction of the film at an angle of 45 degrees from the slow axis direction to the fast axis direction and in a direction tilted by 50 degrees from the normal direction, the polarizer protective film is a polyester film, and has a retardation (Rob(45)) of 7,500 nm or more and 11,700 nm or less when measured in an in-plane direction of the film from the slow axis direction toward the fast axis direction at an angle of 45 degrees and in a direction tilted by 50 degrees from the normal direction; The image display device includes light incident on the at least one polarizing plate, and the light includes excited emission from a red phosphor activated with a tetravalent manganese ion.

4. An image display device having an image display cell and at least one polarizing plate, The at least one polarizing plate has a polarizer and at least one polarizer protection film, the retardation (Rob(45)) of the at least one polarizer protective film measured in a direction inclined by 50 degrees from the normal direction at an angle of 45 degrees from the slow axis direction toward the fast axis direction in an in-plane direction of the film is 7,500 nm or more and 11,700 nm or less, both of which are measured at 100 mm intervals along the long side direction and at 100 mm intervals along the short side direction; a value obtained by subtracting the maximum value from the minimum value of the values ​​measured at 100 mm intervals along the long side direction of Rob (45), and a value obtained by subtracting the maximum value from the minimum value of the values ​​measured at 100 mm intervals along the short side direction of Rob (45) are both 500 nm or less, the at least one polarizer protective film is a polyester film; The image display device includes light incident on the at least one polarizing plate, and the light includes excited emission from a red phosphor activated with a tetravalent manganese ion.

5. A liquid crystal display device having a backlight light source, a light source side polarizing plate, a liquid crystal cell, and a viewer side polarizing plate, the emission spectrum of the backlight light source has a plurality of peaks in the range of 600 to 650 nm; At least one of the light source-side polarizing plate and the viewer-side polarizing plate is a polarizing plate having a polarizer protective film having a 45-degree light source compatibility index (FI(45)) calculated by the following formula 1 of 0.4 to 0.62, The liquid crystal display device, wherein the polarizer protective film having a 45-degree light source compatibility index (FI(45)) of 0.4 or more and 0.62 or less is a polyester film. FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1 Rob(45): Retardation when the polarizer protective film is measured in the in-plane direction of the film at an angle of 45 degrees from the slow axis direction to the fast axis direction and inclined by 50 degrees from the normal direction. Wd: Peak-to-peak distance (nm) Wc: central wavelength of the peak group (nm)

6. A liquid crystal display device having a backlight light source, a light source side polarizing plate, a liquid crystal cell, and a viewer side polarizing plate, the emission spectrum of the backlight light source has a plurality of peaks in the range of 600 to 650 nm; At least one of the light source side polarizing plate and the viewer side polarizing plate has a polarizer and at least one polarizer protective film, The at least one polarizer protective film has a 45-degree light source compatibility index (FI(45)) calculated by the following formula 1, the FI(45) being measured at 100 mm intervals along the long side direction and the FI(45) being measured at 100 mm intervals along the short side direction, both of which are 0.4 or more and 0.62 or less, The value obtained by subtracting the maximum value from the minimum value of the FI(45) measured at 100 mm intervals along the long side direction, and the value obtained by subtracting the maximum value from the minimum value of the FI(45) measured at 100 mm intervals along the short side direction are both 0.026 or less, The at least one polarizer protective film is a polyester film. FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1 Rob(45): Retardation when the polarizer protective film is measured in the in-plane direction of the film at an angle of 45 degrees from the slow axis direction to the fast axis direction and inclined by 50 degrees from the normal direction. Wd: Peak-to-peak distance (nm) Wc: central wavelength of the peak group (nm)

7. A liquid crystal display device having a backlight light source, a light source side polarizing plate, a liquid crystal cell, and a viewer side polarizing plate, The backlight source emits red phosphors activated with tetravalent manganese ions by excitation light, at least one of the light source-side polarizing plate and the viewer-side polarizing plate is a polarizing plate having a polarizer protective film having a retardation (Rob(45)) of 7,500 nm or more and 11,700 nm or less when measured in an in-plane direction of the film at an angle of 45 degrees from the slow axis direction to the fast axis direction and in a direction tilted by 50 degrees from the normal direction, The liquid crystal display device, wherein the polarizer protective film is a polyester film, and the retardation (Rob(45)) measured in a direction inclined by 50 degrees from the normal direction at an angle of 45 degrees from the slow axis direction toward the fast axis direction in the in-plane direction of the film is 7,500 nm or more and 11,700 nm or less.

8. A liquid crystal display device having a backlight light source, a light source side polarizing plate, a liquid crystal cell, and a viewer side polarizing plate, The backlight source emits red phosphors activated with tetravalent manganese ions by excitation light, At least one of the light source side polarizing plate and the viewer side polarizing plate has a polarizer and at least one polarizer protective film, the retardation (Rob(45)) of the at least one polarizer protective film measured in a direction inclined by 50 degrees from the normal direction at an angle of 45 degrees from the slow axis direction toward the fast axis direction in an in-plane direction of the film is 7,500 nm or more and 11,700 nm or less, both of which are measured at 100 mm intervals along the long side direction and at 100 mm intervals along the short side direction; a value obtained by subtracting the maximum value from the minimum value of the values ​​measured at 100 mm intervals along the long side direction of Rob (45), and a value obtained by subtracting the maximum value from the minimum value of the values ​​measured at 100 mm intervals along the short side direction of Rob (45) are both 500 nm or less, The at least one polarizer protective film is a polyester film.

9. A method for selecting a combination of a backlight light source and a polarizing plate in a liquid crystal display device having a backlight light source, a light source side polarizing plate, a liquid crystal cell, and a viewer side polarizing plate, comprising the steps of: (a) selecting a backlight source having an emission spectrum with a plurality of peaks in the range of 600-650 nm; and (b) selecting at least one of the light source side polarizing plate and the viewer side polarizing plate, the polarizing plate having a polarizer protective film having a 45 degree light source compatibility index (FI(45)) calculated by the following formula 1 of 0.4 to 0.62; Including, The polarizer protective film having a 45-degree light source compatibility index (FI(45)) of 0.4 to 0.62 is a polyester film. FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1 Rob(45): Retardation when the polarizer protective film is measured in the in-plane direction of the film at an angle of 45 degrees from the slow axis direction to the fast axis direction and inclined by 50 degrees from the normal direction. Wd: Peak-to-peak distance (nm) Wc: central wavelength of the peak group (nm)

10. A method for selecting a combination of a backlight light source and a polarizing plate in a liquid crystal display device having a backlight light source, a light source side polarizing plate, a liquid crystal cell, and a viewer side polarizing plate, comprising the steps of: (a) selecting a backlight source having an emission spectrum with a plurality of peaks in the range of 600-650 nm; and (b) at least one of the light source side polarizing plate and the viewer side polarizing plate, A process for selecting a polarizing plate having a polarizer protective film in which a 45-degree light source compatibility index (FI(45)) calculated by the following formula 1, measured at 100 mm intervals along the long side direction and at 100 mm intervals along the short side direction, is 0.4 to 0.62 in both cases, and a value obtained by subtracting the maximum value from the minimum value of the FI(45) measured at 100 mm intervals along the long side direction and a value obtained by subtracting the maximum value from the minimum value of the FI(45) measured at 100 mm intervals along the short side direction are both 0.026 or less; Including, the polarizer protective film in which both of a value obtained by subtracting the maximum value from the minimum value of the FI(45) measured at 100 mm intervals along the long side direction and a value obtained by subtracting the maximum value from the minimum value of the FI(45) measured at 100 mm intervals along the short side direction are 0.026 or less, is a polyester film. FI(45)=Wd / [Wc / (Rob(45) / Wc)] Equation 1 Rob(45): Retardation when the polarizer protective film is measured in the in-plane direction of the film at an angle of 45 degrees from the slow axis direction to the fast axis direction and inclined by 50 degrees from the normal direction. Wd: Peak-to-peak distance (nm) Wc: central wavelength of the peak group (nm)